Catalyst systems for crystallizable reactor-grade resins

By combining the titanium-antimony catalyst system with the phosphorus compound, the problems of low reactivity and poor color of neopentyl glycol (NPG) in the polyester composition are solved, and the production of highly efficient and excellent colored crystalline polyester compositions is achieved.

CN114729113BActive Publication Date: 2025-03-18EASTMAN CHEM CO
View PDF 34 Cites 0 Cited by

Patent Information

Application Number
CN202080084953.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-08
Filing Date
2020-10-08
Publication Date
2025-03-18
Estimated Expiration
2040-10-08

AI Technical Summary

Technical Problem

In the production of crystallizable polyester compositions containing neopentyl glycol (NPG), prior art encounters problems with low reactivity, extreme reaction conditions and high excess loading, while conventional catalyst systems lead to poor product color and severe degradation of diols.

Method used

The titanium-antimony catalyst system is used to combine with the phosphorus compound to prepare a crystalline copolyester composition containing NPG, and the polymerization rate and color performance are improved by adjusting the concentration and composition of the catalyst.

Benefits of technology

A crystalline polyester composition with excellent color is achieved at the same or improved polymerization rate, avoiding the degradation of diols and the incorporation of poor end groups, meeting commercial performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114729113B_ABST
    Figure CN114729113B_ABST
Patent Text Reader

Abstract

The present disclosure relates to catalyst systems for producing crystallizable polyester compositions comprising residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) within specific composition ranges having certain advantages and improved properties, including recyclability.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present disclosure relates to catalyst systems for producing crystallizable polyester compositions comprising residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) within specific composition ranges having certain advantages and improved properties, including recyclability. Background of the Invention

[0003] Polyester compositions containing certain moderately reactive diols, such as neopentyl glycol (NPG, 2,2-dimethyl-1,3-propanediol), are well known and used in a variety of applications. However, these diols are generally less reactive in esterification reactions than other diols, such as ethylene glycol (EG) or 1,4-cyclohexanedimethanol (CHDM), and production of compositions containing these diols may require extreme reaction conditions, high overloadings of the diol, specialized catalysts, staged reactant addition, or some combination of these variables to achieve the desired product molecular weight at reasonable production rates. Furthermore, conventional measures to increase production rates and diol incorporation in compositions made from these diols often result in higher levels of diol degradation, poor product color, undesirable polymer end group groups, and poor diol incorporation in polyesters made from combinations with other diols.

[0004] In the past, pure titanium catalysts were the preferred catalysts for producing copolyester compositions made from a combination of terephthalic acid (TPA), ethylene glycol (EG), 1,4-cyclohexanedimethanol (CHDM), and diethylene glycol (DEG). These catalyst systems typically contained 20-25 ppm of titanium and 25 ppm of phosphorus, which acted as a moderator. However, these pure titanium systems are not suitable for the crystallizable polyester compositions of the present disclosure because NPG is included in these compositions.

[0005] In the present disclosure, crystallizable polyester compositions comprising residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) have been discovered that can be recovered in a PET recycle stream. The inclusion of NPG in these crystallizable polyester compositions necessitates a novel catalyst system. Specifically, the color of the polyesters of the present disclosure exhibits extremely high b* values ​​(i.e., their color is very yellow) when prepared using a pure titanium catalyst system. An increase in phosphorus loading is not effective in alleviating the high yellow color, although the polymerization rate is reduced. Reducing the titanium content brings a slight color improvement, but it results in a reduction in the polymerization rate as measured by monitoring the inherent viscosity achieved over time.

[0006] It has been discovered that a titanium-antimony catalyst system, when used with a phosphorus compound, produces polyester compositions having much better color at the same or improved polymerization rates compared to compositions made using the pure titanium system.

[0007] There is a commercial need for crystallizable polyester compositions that are recyclable in PET recycling streams that exhibit good performance properties. There is a commercial need for catalyst systems for producing crystallizable polyester compositions having good polymerization rates and good color. SUMMARY OF THE INVENTION

[0009] It has been found that certain combinations of diol monomers can be made into crystallizable polyester compositions so that they do not affect the recovery of the PET that accompanies them in the recycling process. Articles made using these crystallizable polyester resins can be processed together with PET articles and ultimately become components in recyclable PET flakes that leave the recycling process. It has also been found that the selection and amount of a specific combination of diol monomers are important for producing polyesters that have good performance properties and are crystallizable. The optimized polyester resin compositions of the present disclosure are amorphous but crystallizable. Therefore, they exhibit good properties in applications such as films and sheets, including as shrink films and thermoformable sheets, but they have a high strain-induced crystallization melting point, so they provide compatibility in the recycling process. Articles made with the polyester compositions of the present disclosure do not have to be removed during the recycling process, and they do not affect the recycling process.

[0010] It has also been found that a catalyst system comprising a low amount of a titanium compound in combination with an antimony compound and comprising a phosphorus compound produces a crystallizable copolyester composition comprising neopentyl glycol having better color and equivalent reaction rates than a more conventional pure titanium system comprising phosphorus as a stabilizer / catalyst moderator. The low titanium-antimony combination is effective over a wide temperature range and at the highest phosphorus content disclosed, reaction temperatures in excess of 300°C can be used without sacrificing product color.

[0011] In one embodiment, heat-shrinkable films made from the crystallizable polyester compositions of the present disclosure must meet various suitability criteria. The films must be strong, they must shrink in a controlled manner, and they must provide sufficient shrinkage force to hold themselves to the bottle without crushing the contents. In addition, when these labels are applied to polyester containers or bottles, these polyester shrink film labels must not interfere with the recycling process of the polyester containers or bottles. The shrink films of the present disclosure are advantageous because the labels can be recycled with the bottles or containers. Thus, the entire container or bottle, including the label, can be recycled and converted into new products without incurring additional handling requirements or creating new environmental issues. Heat-shrinkable films are made from a variety of raw materials to meet a range of material requirements. The present disclosure describes unique and unexpected effects measured with certain monomer combinations for shrink film resin compositions.

[0012] Polyester shrink film compositions have been used commercially as shrink film labels for food, beverages, personal care, household products, and the like. Typically, these shrink films are used in combination with clear polyethylene terephthalate (PET) bottles or containers. The entire package (bottle plus label) is then put into the recycling process. At a typical recycling center, the PET and shrink film materials can end up together at the end of the process due to the similarity in composition and density. The PET bottle flakes need to be dried to remove residual water that is left in the PET through the recycling process. Typically, the PET is dried at temperatures above 200°C. At these temperatures, typical polyester shrink film resins soften and become sticky, often forming clumps with the PET bottle flakes. These clumps must be removed before further processing. These clumps reduce the yield of PET bottle flakes from the process and result in additional handling steps. In one aspect of the present disclosure, caking evaluation is performed using the APR caking test: PET-S-08 PET Flake Clumping Evaluation (revised on November 16, 2018), and the determination of suitability for recycling streams is performed in accordance with "Critical Guidance Protocol for Clear PET Articles with Labels and Closures", dated April 11, 2019, Document No. PET-CG-02.

[0013] In the present disclosure, it has been discovered that certain combinations of diol monomers can make compositions that have good performance properties in polyester compositions and that can also crystallize so that they do not affect the recycling of PET. It has also been discovered that certain combinations of diol monomers can make films or sheets that have good performance properties in film or sheet resin compositions and that can also crystallize so that they do not affect the recycling of PET bottle flakes. These crystallizable film or sheet resins can be processed with recycled PET and ultimately become a component in recycled PET bottle flakes that exit the recycling process. It has also been discovered that the selection and amount of a particular combination of diol monomers is important for producing films or sheets with good performance properties and for producing films or sheets that can crystallize. In other words, the polyester compositions of the present disclosure are amorphous, but they are "crystallizable" in the sense of having a high strain-induced crystalline melting point. Thus, they exhibit good properties in film or sheet applications, including shrink films, molded, thermoformed or formed parts and / or articles, but they also have a high strain-induced crystalline melting point, so they can be recycled with PET because when recycled PET bottle flakes are subjected to high temperature drying conditions, the crystallizable polyesters of the present disclosure do not form lumps that would hinder the normal mechanical operation of flaking, drying and feeding the bottle flakes into an extruder for further processing into (recycled) polyester pellets. Similarly, extruded sheets made from the resin compositions of the present disclosure do not have to be removed during the recycling process and therefore do not adversely affect the recycling process. (See, e.g., https: / / www.thebalancesmb.com / recycling-polyethylene-terephthalate-pet- 2877869 ).

[0014] One embodiment of the present disclosure is a crystallizable reactor-grade polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 75 mole % or more of ethylene glycol residues and about 25 mole % or less of other diols, the other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole % neopentyl glycol residues; (ii) 0 to less than about 24 mole % 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %.

[0015] One embodiment of the present disclosure is a crystallizable reactor-grade polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues and about 20 mole % or less of other diols, the other diols comprising: (i) about 5 to less than about 17 mole % neopentyl glycol residues; (ii) about 2 to less than about 10 mole % 1,4-cyclohexanedimethanol residues; (iii) about 1 to less than about 5 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %.

[0016] One embodiment of the present disclosure is a crystallizable reactor-grade polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 76 mole % or more of ethylene glycol residues and about 24 mole % or less of amorphous content selected from: (i) neopentyl glycol residues; (ii) cyclohexanedimethanol residues; and (iii) diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %.

[0017] One embodiment of the present disclosure is a crystallizable reactor-grade polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 1 to about 30 mole % of neopentyl glycol residues; (ii) from about 1 to about less than 30 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1.5 to 6 mole % of diethylene glycol residues; and wherein the remaining diol component comprises: (iv) ethylene glycol residues, and (v) 0 to 20 mole % of residues of at least one modifying diol; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %.

[0018] One embodiment of the present disclosure is the crystallizable reactor-grade polyester composition of any preceding embodiment, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system comprising 2 to 15 ppm titanium, 50 to 150 ppm antimony, and 0 to 60 ppm phosphorus, wherein the concentration of the residue of the catalyst system is based on the weight of the polyester.

[0019] One embodiment of the present disclosure is the crystallizable reactor-grade polyester composition of any preceding embodiment, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system comprising 3 to 10 ppm titanium, 50 to 125 ppm antimony, and 0 to 50 ppm phosphorus, wherein the concentration of the residue of the catalyst system is based on the weight of the polyester.

[0020] One embodiment of the present disclosure is the crystallizable reactor-grade polyester composition of any preceding embodiment, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system containing 4 to 12 ppm titanium, 100 to 120 ppm antimony, and 2 to 50 ppm phosphorus, wherein the amount of the residue of the catalyst system is based on the weight of the polyester.

[0021] One embodiment of the present disclosure is the crystallizable reactor-grade polyester composition of any preceding embodiment, wherein the composition has a strain-induced crystallization melting point of 190°C or more or 200°C or more.

[0022] One embodiment of the present disclosure is the crystallizable reactor-grade polyester composition of any preceding embodiment, wherein the composition has a strain-induced crystallization melting point of 200°C or greater.

[0023] One embodiment of the present disclosure is a crystallizable polyester composition or crystallizable polyester blend comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: from about 75 mole % or more of ethylene glycol residues and from about 25 mole % or less of other diols, the other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole % of neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a diol component comprising: from about 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester or (c) residues of a catalyst system consisting essentially of 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester or (c) residues of a catalyst system consisting of 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester; and wherein the polyester has a strain induced crystallization melting point of 190°C or more or 200°C or more.

[0024] One embodiment of the present disclosure is a method for preparing a crystallizable reactor-grade polyester composition, comprising: (a) reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues and ethylene glycol residues in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound to produce an esterification product; wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; (b) prepolymerizing the esterification product in the presence of 0 to 60 ppm of a phosphorus stabilizer to produce a polycondensation product, wherein the prepolymerization temperature is 255 to 275° C. and the pressure is 200-500 mmHg; (c) finishing the polycondensation product to produce a polyester, wherein the polyester has a carbon content of at least 0.50 dL / g or an inherent viscosity of 0.50-0.90 dL / g, and wherein the finishing polymerization temperature is elevated to 280-320°C and the pressure is 0.3 to 7 mmHg.

[0025] One embodiment of the present disclosure is a method for preparing a crystallizable reactor-grade polyester composition, comprising: (a) reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues, and ethylene glycol residues to produce an esterification product, wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; (b) prepolymerizing the esterification product in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound, and 0 to 90 ppm of a phosphorus stabilizer to produce a prepolymerized polycondensation product, wherein the polycondensation temperature is 255 to 275° C.; and (c) post-treating the polycondensation product to produce a polyester, wherein the polyester has an inherent viscosity of at least 0.50 dL / g or 0.50-0.90 dL / g, and wherein the post-treatment polymerization temperature is elevated to 280 to 320° C. and the pressure is 0.3 to 7 mmHg.

[0026] One embodiment of the present disclosure is the method of any preceding embodiment, wherein the polyester has good color or a b* of 20 or less.

[0027] One embodiment of the present disclosure is a catalyst system for producing a crystallizable reactor-grade polyester composition comprising: 2-15 ppm of a titanium compound, 50-150 ppm of an antimony compound, and 0-90 ppm of a phosphorus compound, wherein the polyester composition comprises terephthalic acid, 1,4-cyclohexanedimethanol, neopentyl glycol, ethylene glycol, and diethylene glycol.

[0028] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: from about 75 mole % or more of ethylene glycol residues and from about 25 mole % or less of other diols, the other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole % of neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a diol component comprising: from about 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus residues of the catalyst system, wherein the concentration of the catalyst system residues is based on the weight of the polyester.

[0029] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: from about 75 mole % or more of ethylene glycol residues and from about 25 mole % or less of other diols, the other diols comprising one or more of: (i) 0 to less than about 24 mole % of neopentyl glycol residues; (ii) from about 0 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a polyol component comprising from 2 to 15 ppm titanium, 50 to 150 ppm tantalum, and 2 to 15 ppm tantalum. ppm antimony and 0 to 60 ppm phosphorus of a catalyst system residue, wherein the concentration of the catalyst system residue is based on the weight of the polyester.

[0030] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: from about 75 mole % or more of ethylene glycol residues and from about 25 mole % or less of other diols, the other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole % of neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a diol component comprising: from about 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus residues of the catalyst system, wherein the concentration of the catalyst system residues is based on the weight of the polyester.

[0031] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues and about 20 mole % or less of other diols, the other diols comprising: (i) about 5 to less than about 17 mole % of neopentyl glycol residues; (ii) about 2 to less than about 10 mole % of 1,4-cyclohexanedimethanol residues; (iii) about 1 to less than about 5 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a polyol component comprising 2 to 15 ppm titanium, 50 to 150 ppm tantalum, and 2 to 15 ppm tantalum. ppm antimony and 0 to 60 ppm phosphorus of a catalyst system residue, wherein the concentration of the catalyst system residue is based on the weight of the polyester.

[0032] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 76 mole % or more of ethylene glycol residues and about 24 mole % or less of amorphous content comprising (i) neopentyl glycol residues; (ii) cyclohexanedimethanol residues; and (iii) diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a residue of a catalyst system containing 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the concentration of the residue of the catalyst system is based on the weight of the polyester.

[0033] One embodiment of the present disclosure is a crystallizable film comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 1 to about 30 mole % of neopentyl glycol residues; (ii) from about 1 to about less than 30 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1.5 to 6 mole % of diethylene glycol residues, whether or not formed in situ; and wherein the remaining diol component comprises: (iv) ethylene glycol residues, and (v) 0 to 10 mole % of residues of at least one modifying diol; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %; and (c) a diol component comprising 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus residues of the catalyst system, wherein the concentration of the catalyst system residues is based on the weight of the polyester.

[0034] One embodiment of the present disclosure is the crystallizable film of any of the preceding embodiments, wherein the film is stretched in at least one direction and the stretched film has a strain-induced crystalline melting point of 190° C. or higher.

[0035] One embodiment of the present disclosure is the crystallizable film of any of the preceding embodiments, wherein the film is stretched in at least one direction and the stretched film has a strain-induced crystalline melting point of 200° C. or higher.

[0036] One embodiment of the present disclosure is the crystallizable film of any of the preceding embodiments, wherein the film is stretched in at least one direction and the stretched film has a strain-induced crystalline melting point of 190°C - 200°C.

[0037] One embodiment of the present disclosure is an extruded or calendered film comprising the crystallizable film of any of the preceding embodiments.

[0038] One embodiment of the present disclosure is a thermoforming sheet comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole % of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: from about 75 mole % or more of ethylene glycol residues and from about 25 mole % or less of other diols, the other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole % of neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a diol component comprising from 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus residues of the catalyst system, wherein the concentration of the catalyst system residues is based on the weight of the polyester.

[0039] One embodiment of the present disclosure is a thermoforming sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues and about 20 mole % or less of other diols, the other diols comprising one or more of the following: (i) about 5 to less than about 17 mole % neopentyl glycol residues; (ii) about 2 to less than about 10 mole % 1,4-cyclohexanedimethanol residues; (iii) about 1 to less than about 5 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole %, and wherein the total mole % of the diol component is 100 mole %; and (c) A catalyst system residue containing 2 to 15 ppm titanium, 50 to 150 ppm antimony, and 0 to 60 ppm phosphorus, wherein the concentration of the catalyst system residue is based on the weight of the polyester.

[0040] One embodiment of the present disclosure is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 76 mole % or more of ethylene glycol residues and about 24 mole % or less of an amorphous content comprising one or more of: (i) neopentyl glycol residues; (ii) cyclohexanedimethanol residues; and (iii) diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a polyester containing 2 to 15 ppm titanium, 50 to 150 ppm antimony, and 0 to 60 ppm phosphorus of the catalyst system residues, wherein the concentration of the catalyst system residues is based on the weight of the polyester.

[0041] One embodiment of the present disclosure is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) about 1 to about 30 mole % of neopentyl glycol residues; (ii) about 1 to about less than 30 mole % of 1,4-cyclohexanedimethanol residues; and (iii) about 1.5 to about 6 mole % of diethylene glycol residues, whether or not formed in situ; and wherein the remaining diol component comprises: (iv) ethylene glycol residues, and (v) Optionally, 0 to 10 mol %, or 0 to 5 mol % of residues of at least one modifying diol; wherein the total mol % of the dicarboxylic acid components is 100 mol %, and wherein the total mol % of the diol components is 100 mol %; and (c) residues of a catalyst system containing 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the concentration of the residues of the catalyst system is based on the weight of the polyester.

[0042] One embodiment of the present disclosure is a molded, thermoformed or shaped article comprising or prepared from the sheet of any of the preceding embodiments, wherein the sheet has a strain-induced crystalline melting point of 190° C. or higher.

[0043] One embodiment of the present disclosure is a molded, thermoformed or shaped article comprising or prepared from the sheet of any of the preceding embodiments, wherein the sheet has a strain-induced crystalline melting point of 200° C. or higher.

[0044] One embodiment of the present disclosure is a molded, thermoformed or shaped article comprising or prepared from the sheet of any preceding embodiment, wherein the sheet has a strain induced crystallization melting point of 190°C - 215°C.

[0045] One embodiment of the present disclosure is a molded, thermoformed or shaped article comprising or prepared from the sheet of any of the preceding embodiments.

[0046] One embodiment of the present disclosure is an article selected from medical device packaging, medical packaging, healthcare product packaging, commercial food service products, trays, containers, food trays, tumblers, storage bins, bottles, food processors, blender and mixer bowls, utensils, water bottles, crisper trays, washing machine parts, refrigerator parts, vacuum cleaner parts, ophthalmic lenses and frames or toys, comprising or prepared from a sheet of any preceding embodiment.

[0047] One embodiment of the present disclosure is a method of making a molded or thermoformed article or part from a sheet of any of the foregoing embodiments, comprising: A. heating a sheet comprising a polyester composition of the present disclosure; B. applying air pressure, vacuum and / or physical pressure to the heat softened sheet; C. causing the sheet to conform to the shape of a mold by vacuum or pressure; D. cooling the formed sheet to below its T g temperature and E. Removal of a molded or thermoformed part or article from a mold.

[0048] One embodiment of the present disclosure is a polyester recycle stream comprising recycled poly(ethylene terephthalate) bottle flakes having admixed therewith at least about 0.1 wt. % of the crystallizable recycled shrink film of the present disclosure.

[0049] One embodiment of the present disclosure is a polyester recycle stream comprising recycled poly(ethylene terephthalate) bottle flakes having admixed therewith at least about 0.1 wt. % of the crystallizable reactor grade polyester composition of the present disclosure.

[0050] One embodiment of the present disclosure is a polyester recycle stream comprising recycled poly(ethylene terephthalate) bottle flakes having admixed therewith at least about 0.1 wt. % of the crystallizable recycled thermoformable sheet of the present disclosure.

[0051] One embodiment of the present disclosure is a polyester recycling stream comprising recycled polyethylene terephthalate bottle flakes having mixed therewith at least about 0.1 wt. % of the crystallizable recycled shrink film of the present disclosure, wherein the stream passes The Association for Plastic Recyclers (APR) test PET-CG-02.

[0052] The crystallizable compositions of the present disclosure thus constitute an advantageous component of a PET recycling stream, since such compositions can accompany the PET in the recycling stream without the need for an additional separation step. Accordingly, in one embodiment of the present disclosure, there is provided a polyester recycling stream comprising recycled polyethylene terephthalate bottle flakes having at least about 0.1% by weight of the crystallizable compositions of the present disclosure mixed therewith. In another embodiment, wherein the stream passes through "Critical Guidance Protocol for Clear PET Articles with Labels and Closures", dated April 11, 2019, Document No. PET-CG-02.

[0053] One embodiment of the present disclosure is a crystallizable polyester composition comprising: at least one polyester comprising: (a) a dicarboxylic acid component comprising: (i) about 70 to about 100 mole % of terephthalic acid residues; (ii) about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 75 mole % or more of ethylene glycol residues and about 25 mole % or less of other diols, the other diols comprising one or more of the following: (i) about 0.1 to less than about 24 mole % of neopentyl glycol residues; (ii) about 0.1 to less than about 24 mole % of 1,4-cyclohexanedimethanol residues; (iii) about 1 to less than about 10 mole % of the total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid component is 100 mole % and wherein the total mole % of the diol component is 100 mole %; and (c) a polyol component comprising 2 to 15 ppm titanium, 50 to 150 ppm tantalum, 2 to 3 ppm tantalum, 1 to 2 ppm tantalum, 1 ...3 ppm tantalum, 1 to 2 ppm tantalum, 1 to 3 ppm tantalum, 1 to 3 ppm tantalum ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester or (c) residues of a catalyst system consisting essentially of 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester or (c) residues of a catalyst system consisting of 2 to 15 ppm titanium, 50 to 150 ppm antimony and 0 to 60 ppm phosphorus, wherein the amount of the catalyst system residue is based on the weight of the polyester; and wherein the polyester has a strain induced crystallization melting point of 190°C or more or 200°C or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is a graph of % PET agglomerates vs. relative crystallinity. The triangular points represent more than 1% PET agglomerates. The circular points represent less than 1% PET agglomerates and therefore pass the "Critical Guidance Protocol for Clear PET Articles with Labels and Closures", dated April 11, 2019, Document No. PET-CG-02.

[0056] Details

[0057] The disclosure is more easily understood with reference to the following detailed description of certain embodiments and examples of the disclosure. According to one or more purposes of the disclosure, certain embodiments of the disclosure are described in the Summary of the Invention and are further described below. Other embodiments of the disclosure are also described herein.

[0058] It has been discovered in the present disclosure that certain combinations of diol monomers in a polyester composition can produce a crystallizable polyester resin having good performance properties and, because it can also crystallize, it does not affect the recovery of PET bottle flakes in the recycling process. Articles made using the crystallizable resins of the present disclosure, including shrink films and thermoformable sheets, can be processed with PET bottles and ultimately become a component in the recycled PET bottle flakes exiting the recycling process. It has also been discovered that the selection and amount of a particular combination of diol monomers is important to produce articles, such as films or sheets (including shrink films), that have good performance properties and can crystallize.

[0059] The term "polyester" as used herein is intended to include "copolyesters" and is understood to refer to synthetic polymers made by the reaction of one or more difunctional carboxylic acids and / or polyfunctional carboxylic acids with one or more difunctional hydroxyl compounds and / or polyfunctional hydroxyl compounds, such as branching agents. Typically, the difunctional carboxylic acid can be a dicarboxylic acid, and the difunctional hydroxyl compound can be a dihydric alcohol, such as glycols and diols. The term "diol" as used herein includes, but is not limited to, diols, glycols and / or polyfunctional hydroxyl compounds, such as branching agents. Alternatively, the difunctional carboxylic acid can be a hydroxycarboxylic acid, such as p-hydroxybenzoic acid, and the difunctional hydroxyl compound can have an aromatic core with 2 hydroxyl substituents, such as hydroquinone. The term "residue" as used herein refers to any organic structure incorporated into a polymer from the corresponding monomer by polycondensation and / or esterification reactions. The term "repeat unit" as used herein refers to an organic structure having a dicarboxylic acid residue and a diol residue bonded via an ester group. Thus, for example, a dicarboxylic acid residue may be derived from a dicarboxylic acid monomer or its associated acyl halides, esters, salts, anhydrides and / or mixtures thereof. In addition, the term "diacid" as used herein includes polyfunctional acids, such as branching agents. Thus, the term "dicarboxylic acid" as used herein is intended to include dicarboxylic acids and any derivatives of dicarboxylic acids that can be used in the process of reacting with a diol to make a polyester, including its associated acyl halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides and / or mixtures thereof. The term "terephthalic acid" as used herein is intended to include terephthalic acid itself and its residues that can be used in the process of reacting with a diol to make a polyester, as well as any derivatives of terephthalic acid, including its associated acyl halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides and / or mixtures thereof or residues thereof.

[0060] The polyester used in the present disclosure can generally be prepared from dicarboxylic acids and diols that react in substantially equal proportions and are incorporated into the polyester polymer as their corresponding residues. The polyester of the present disclosure may therefore contain substantially equal molar proportions of acid residues (100 mole %) and diol (and / or multifunctional hydroxy compound) residues (100 mole %) to make the total mole number of repeating units equal to 100 mole %. Therefore, the mole percentage provided in the present disclosure may be based on the total mole number of acid residues, the total mole number of diol residues, or the total mole number of repeating units. For example, a polyester containing 10 mole % of isophthalic acid based on the total acid residues means that the polyester contains 10 mole % of isophthalic acid residues in a total of 100 mole % of acid residues. Therefore, there are 10 moles of isophthalic acid residues in every 100 moles of acid residues. In another example, a polyester containing 25 mole % of 1,4-cyclohexanedimethanol based on the total diol residues means that the polyester contains 25 mole % of 1,4-cyclohexanedimethanol residues in a total of 100 mole % of diol residues. Thus, there are 25 moles of 1,4-cyclohexanedimethanol residues for every 100 moles of diol residues.

[0061] In certain embodiments, terephthalic acid or its esters, such as dimethyl terephthalate or a mixture of terephthalic acid residues and their esters may constitute part or all of the dicarboxylic acid component used to form the polyester that can be used in the present disclosure. In certain embodiments, terephthalic acid residues may constitute part or all of the dicarboxylic acid component used to form the polyester that can be used in the present disclosure. For the purposes of the present disclosure, the terms "terephthalic acid" and "dimethyl terephthalate" are used interchangeably herein. In one embodiment, dimethyl terephthalate is part or all of the dicarboxylic acid component used to make the polyester that can be used in the present disclosure. In embodiments, 70 to 100 mol%; or 80 to 100 mol%; or 90 to 100 mol%; or a range of 99 to 100 mol%; or 100 mol% terephthalic acid and / or dimethyl terephthalate and / or mixtures thereof may be used.

[0062] In addition to terephthalic acid, the dicarboxylic acid component of the polyester that can be used in the present disclosure may include up to 30 mol%, up to 20 mol%, up to 10 mol%, up to 5 mol% or up to 1 mol% of one or more modified aromatic dicarboxylic acids. Another embodiment contains 0 mol% modified aromatic dicarboxylic acid. Therefore, if present, it is expected that the amount of one or more modified aromatic dicarboxylic acids can start from any of these aforementioned endpoint values, including, for example, 0.01 to 10 mol%, 0.01 to 5 mol% and 0.01 to 1 mol%. In one embodiment, modified aromatic dicarboxylic acids that can be used in the present disclosure include, but are not limited to, those with up to 20 carbon atoms, which can be linear, para-oriented or symmetrical. Examples of modified aromatic dicarboxylic acids that can be used in the present disclosure include, but are not limited to, isophthalic acid, 4,4′-biphenyl dicarboxylic acid, 1,4-, 1,5-, 2,6-, 2,7-naphthalene dicarboxylic acid and trans-4,4′-stilbene dicarboxylic acid, and their esters. In one embodiment, the modifying aromatic dicarboxylic acid is isophthalic acid.

[0063] The carboxylic acid component of the polyester that can be used for the present disclosure can be further modified with up to 10 mol %, such as up to 5 mol % or up to 1 mol % of one or more aliphatic dicarboxylic acids containing 2-16 carbon atoms, such as cyclohexanedicarboxylic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and / or dodecanedicarboxylic acid. Certain embodiments may also include 0.01 to 10 mol %, such as 0.1 to 10 mol %, 1 or 10 mol %, 5 to 10 mol % of one or more modified aliphatic dicarboxylic acids. Another embodiment contains 0 mol % modified aliphatic dicarboxylic acids. The total mole % of the dicarboxylic acid component is 100 mol %. In one embodiment, adipic acid and / or glutaric acid are provided in the modified aliphatic dicarboxylic acid component of the polyester and it can be used for the present disclosure.

[0064] Can use esters of terephthalic acid and other modified dicarboxylic acids or their corresponding esters and / or salts to replace dicarboxylic acids. Suitable examples of dicarboxylic acid esters include but are not limited to dimethyl ester, diethyl ester, dipropyl ester, diisopropyl ester, dibutyl ester and diphenyl ester. In one embodiment, the ester is selected from at least one of the following: methyl ester, ethyl ester, propyl ester, isopropyl ester and phenyl ester.

[0065] In one embodiment, the diol component useful for the crystallizable polyester composition of the present disclosure may include 1,4-cyclohexanedimethanol. In another embodiment, the diol component useful for the crystallizable polyester composition of the present disclosure may include 1,4-cyclohexanedimethanol and 1,3-cyclohexanedimethanol. The molar ratio of cis / trans 1,4-cyclohexanedimethanol may range from 50 / 50 to 0 / 100, for example, from 40 / 60 to 20 / 80.

[0066] In certain embodiments, the diol component useful for the crystallizable polyester composition of the present disclosure may include, but is not limited to, wherein the sum of the residues of 1,4-cyclohexanedimethanol and the residues of neopentyl glycol in the final polyester composition is 1 to 30 mol%, or 1 to 25 mol%, 1 to 20 mol%, or 1 to 15 mol%, or 1 to 10 mol%, or 2 to 30 mol%, or 2 to 25 mol%, or 2 to 20 mol%, or 2 to 15 mol%, or 2 to 10 mol%, or 3 to 30 mol%, or 3 to 25 mol%, or 3 to 20 mol%, or 3 to 15 mol%, or 3 to 10 mol%, 4 to 30 mol%, or 4 to 25 mol%, or 4 to 20 mol%. %, or 4 to 15 mol%, or 4 to 10 mol%, or 5 to 30 mol%, or 5 to 25 mol%, 5 to 20 mol%, or 5 to 15 mol%, or 5 to 10 mol%, 6 to 30 mol%, or 6 to 25 mol%, 6 to 20 mol%, or 6 to 15 mol%, or 6 to 10 mol%, 7 to 30 mol%, or 7 to 25 mol%, 7 to 20 mol%, or 7 to 15 mol%, or 7 to 10 mol%, 8 to 30 mol%, or 8 to 25 mol%, 8 to 20 mol%, or 8 to 15 mol%, or 8 to 10 mol%, 9 to 30 mol%, or 9 to 25 mol%, 9 to 20 mol%, or 9 to 15 mol%, or 9 to 10 mol%, 10 to 30 mol%, or 10 to 25 mol%, 10 to 20 mol%, or 10 to 15 mol%, or 11 to 30 mol%, 11 to 30 mol%, or 11 to 25 mol%, 11 to 20 mol%, or 11 to 15 mol%, or 12 to 30 mol%, 12 to 25 mol%, or 12 to 20 mol%, 12 to 15 mol%, or 13 to 30 mol%, or 13 to 25 mol%, 13 to 20 mol%, or 13 to 15 mol%, 14 to 30 mol%, or 14 to 25 mol%, or 14 to 20 mol%, 14 to 15 mol%, or 15 to 30 mol%, 15 to 25 mol%, or 15 %, or 11 to 29 mol%, or 12 to 29 mol%, or 13 to 29 mol%, or 14 to 29 mol%, or 15 to 29 mol%, or 10 to 28 mol%, or 11 to 28 mol%, or 12 to 28 mol%, or 13 to 28 mol%, or 14 to 28 mol%, or 15 to 28 mol% of the composition.In one embodiment, the sum of the residues of 1,4-cyclohexanedimethanol and the residues of neopentyl glycol in the final polyester composition may be 1 to 16 mol%, 2 to 14 mol%, 4 to 15 mol%, or 2 to 21 mol%, or 2 to less than 20 mol%, or 4 to 20 mol%, or 5 to 18 mol%, or 10 to 21 mol%, or 12 to 21 mol%, wherein the total mol% of the diol components is 100 mol%.

[0067] In one embodiment, the diol component that can be used for the crystallizable polyester composition of the present disclosure may contain 0 to 30 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the crystallizable polyester composition of the present disclosure may contain 0.1 to 30 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the crystallizable polyester composition of the present disclosure may contain 1 to 30 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 1 to 25 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 1 to 17 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 5 to 20 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 10 to 20 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 10 to 15 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 15 to 25 mol% of neopentyl glycol based on the total mol% of the diol component being 100 mol%.

[0068] In one embodiment, the diol component useful for the crystallizable polyester composition of the present disclosure may contain 0 to 30 mol%, or 0.01 to 30 mol%, or 1 to 30 mol%, or 2 to 30 mol%, or 0 to 20 mol%, or 0.1 to 20 mol%, or 1 to 20 mol%, or 2 to 20 mol%, or 0 to 15 mol%, or 0.01 to 15 mol%, or 1 to 15 mol%, or 2 to 15 mol%, or 0.01 to 14 mol%, or 0.01 to 13 mol%, or 0.01 to 12 mol%, or 0.01 to 11 mol%, or 0.0 1 to 10 mol%, or 0.01 to 9 mol%, or 0.01 to 8 mol%, or 0.01 to 7 mol%, or 0.01 to 6 mol%, or 0.01 to 5 mol%, or 3 to 15 mol%, or 3 to 14 mol%, or 3 to 13 mol%, or 3 to 12 mol%, or 3 to 11 mol%, or 3 to 10 mol%, or 3 to 9 mol%, or 3 to 8 mol%, or 3 to 7 mol%, or 2 to 10 mol%, or 2 to 9 mol%, or 2 to 8 mol%, or 2 to 7 mol%, or 2 to 5 mol%, or 1 to 7 mol%, or 1 to 5 mol%, or 1 to 3 mol% of 1,4-cyclohexanedimethanol residues.

[0069] In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 0.01 to 15 mol% of 1,4-cyclohexanedimethanol based on the total mol% of the diol component as 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 0 to less than 15 mol% of 1,4-cyclohexanedimethanol based on the total mol% of the diol component as 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 0.01 to 10 mol% of 1,4-cyclohexanedimethanol based on the total mol% of the diol component as 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 0 to less than 10 mol% of 1,4-cyclohexanedimethanol based on the total mol% of the diol component as 100 mol%. In one embodiment, the diol component that can be used for the polyester composition of the present disclosure may contain 0.01 to 5 mol% of 1,4-cyclohexanedimethanol based on the total mol% of the diol component as 100 mol%. In one embodiment, the diol component useful in the polyester composition of the present disclosure may contain 0 to less than 5 mol % of 1,4-cyclohexanedimethanol based on the total mol % of the diol component being 100 mol %.

[0070] It should be understood that some other diol residues may be formed in situ during processing. In one embodiment, the diol component of the polyester composition as described in the present disclosure may contain any amount of diethylene glycol residues formed in situ during processing and / or intentionally added. For example, in one embodiment, the polyester composition useful in the present disclosure may contain 1 to 15 mol%, or 2 to 12 mol%, or 2 to 11 mol%, or 2 to 10 mol%, or 2 to 9 mol%, or 3 to 12 mol%, or 3 to 11 mol%, or 3 to 10 mol%, or 3 to 9 mol%, or 4 to 12 mol%, or 4 to 11 mol%, or 4 to 10 mol%, or 4 to 9 mol%, or 5 to 12 mol%, or 5 to 11 mol%, or 5 to 10 mol%, or 5 to 9 mol% of diethylene glycol residues based on the total mole % of the diol component being 100 mol%.

[0071] In one embodiment, the total amount of diethylene glycol residues present in the polyester compositions useful in the present disclosure, whether formed in situ during processing or intentionally added, or both, can be 4 mol % or less, or 3.5 mol % or less, or 3.0 mol % or less, or 2.5 mol % or less, or 2.0 mol % or less, or 1.5 mol % or less, or 1.0 mol % or less, or from 1 to 4 mol %, or from 1 to 3 mol %, or from 1 to 2 mol % of diethylene glycol residues, or from 2 to 8 mol %, or from 2 to 7 mol %, or from 2 to 6 mol %, or from 2 to 5 mol %, or from 3 to 8 mol %, or from 3 to 7 mol %, or from 3 to 6 mol %, or from 3 to 5 mol %, or in some embodiments, no intentionally added diethylene glycol residues.

[0072] For all embodiments, the remaining diol component can contain any amount of ethylene glycol residues based on the total mole % of the diol component being 100 mole %. In one embodiment, the polyester portion of the polyester composition useful for the present disclosure can contain 50 mole % or more, or 55 mole % or more, or 60 mole % or more, or 65 mole % or more, or 70 mole % or more, or 75 mole % or more, or 80 mole % or more, or 85 mole % or more, or 90 mole % or more, or 95 mole % or more, or 50 to 85 mole %, or 50 to 80 mole %, or 55 to 80 mole %, or 60 to 80 mole %, or 50 to 75 mole %, or 55 to 75 mole %, or 60 to 75 mole %, or 65 to 75 mole %, or 70 to 80 mole %, or 75 to 85 mole % of ethylene glycol residues based on the total mole % of the diol component being 100 mole %.

[0073] In one embodiment, the diol component of the polyester composition useful in the present disclosure may contain up to 20 mol%, or up to 19 mol%, or up to 18 mol%, or up to 17 mol%, or up to 16 mol%, or up to 15 mol%, or up to 14 mol%, or up to 13 mol%, or up to 12 mol%, or up to 11 mol%, or up to 10 mol%, or up to 9 mol%, or up to 8 mol%, or up to 7 mol%, or up to 6 mol%, or up to 5 mol%, or up to 4 mol%, or up to 3 mol%, or up to 2 mol%, or up to 1 mol% or less of one or more modified diols (modified diols are defined as diols that are not ethylene glycol, diethylene glycol, neopentyl glycol, or 1,4-cyclohexanedimethanol). In certain embodiments, the polyester composition useful in the present disclosure may contain 10 mol% or less of one or more modified diols. In certain embodiments, the polyester useful in the present disclosure may contain 5 mol% or less of one or more modified diols. In certain embodiments, the polyester useful in the present disclosure may contain 3 mol% or less of one or more modified diols. In another embodiment, the polyesters useful in the present disclosure may contain 0 mole % of modifying diols. However, it is contemplated that some other diol residues may be formed in situ such that residual amounts formed in situ are also an embodiment of the present disclosure.

[0074] In an embodiment, if used, the modified glycol for polyester as specified herein contains 2 to 16 carbon atoms. Examples of modified glycols include, but are not limited to, 1,2-propylene glycol, 1,3-propylene glycol, isosorbide, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, p-xylene glycol, polytetramethylene glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), and mixtures thereof. In one embodiment, isosorbide is a modified glycol. In another embodiment, the modified glycol includes, but is not limited to, at least one of 1,3-propylene glycol and 1,4-butanediol. In one embodiment, 1,3-propylene glycol and / or 1,4-butanediol may be excluded. If 1,4- or 1,3-butanediol is used, more than 4 mol % or more than 5 mol % may be provided in one embodiment. In one embodiment, at least one modified glycol is 1,4-butanediol present in an amount of 5 to 25 mol %. In certain embodiments, the polyester compositions are free of added modifying glycols.

[0075] In one embodiment, a crystallizable polyester composition is provided, comprising: 1,4-cyclohexanedimethanol residues present in an amount of 0.01 to about 10 mol %, diethylene glycol residues present in an amount of 2 to 9 mol %, neopentyl glycol residues present in an amount of 5 to 30 mol %, and ethylene glycol residues present in an amount of 60 mol % or more, based on the total mol % of the diol component being 100 mol %.

[0076] In one embodiment, the polyester composition useful in the present disclosure may include at least one chain extender. Suitable chain extenders include, but are not limited to, multifunctional (including but not limited to difunctional) isocyanates, multifunctional epoxides, including, for example, epoxidized novolac resins and phenoxy resins. In certain embodiments, the chain extender may be added at the end of the polymerization process or after the polymerization process. If added after the polymerization process, the chain extender may be incorporated by compounding or by addition during a transformation process, such as injection molding or extrusion.

[0077] In certain embodiments, the amount of chain extender used can vary depending on the specific monomer composition used and the physical properties desired, but is typically from about 0.1 wt % to about 10 wt %, such as from about 0.1 to about 5 wt %, based on the total weight of the polyester.

[0078] Unless otherwise indicated, it is contemplated that the polyester compositions useful in the present disclosure may have at least one inherent viscosity range described herein and at least one monomer range for the polyester compositions described herein. It is also contemplated that the polyester compositions useful in the present disclosure may have at least one T range described herein, unless otherwise indicated. g range and at least one monomer range of the polyester composition described herein. Unless otherwise indicated, it is also expected that the polyester composition useful in the present disclosure may have at least one inherent viscosity range described herein, at least one T g range and at least one monomer range of the polyester compositions described herein.

[0079] For embodiments of the present disclosure, the polyester compositions useful for the present disclosure may exhibit at least one of the following inherent viscosities as measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / dL at 25° C.: 0.50 to 1.2 dL / g; 0.50 to 1.0 dL / g; 0.50 to 0.90 dL / g; 0.50 to 0.80 dL / g; 0.55 to 0.80 dL / g; 0.60 to 0.80 dL / g; 0.65 to 0.80 dL / g; 0.70 to 0.80 dL / g; 0.50 to 0.75 dL / g; 0.55 to 0.75 dL / g; or 0.60 to 0.75 dL / g.

[0080] In one embodiment, the glass transition temperature and strain-induced crystalline melting point (T and T, respectively) of the polyester are determined using a TA DSC 2920 from Thermal Analyst Instrument at a scan rate of 20°C / min. g and T m ). Tm was measured during the first heating of the stretched sample and T was measured during the second heating step. gAdditionally, in another embodiment, the samples can be crystallized in a forced air oven at 165°C for 30 minutes or at 170°C for 2 hours and then analyzed by DSC. For all samples, there is generally no crystalline melting point during the second heating of the DSC scan at a heating rate of 20°C / min.

[0081] In certain embodiments, the oriented film, shrink film, thermoformed sheet of the present disclosure comprises a crystallizable polyester / polyester composition, wherein the polyester has a T of 60 to 80°C; 70 to 80°C; 65 to 80°C; 74 to 77°C, 72 to 77°C, or 65 to 75°C. g In certain embodiments, the polyester has an inherent viscosity of 0.68 to 0.75 dL / g as measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / dL at 25°C, and has a T of 72°C to 77°C as measured using a TA DSC 2920 from Thermal Analyst Instrument at a scan rate of 20°C / min. g .

[0082] In certain embodiments, these T values ​​may be met with or without the addition of at least one plasticizer during the polymerization process or during the extrusion process or during the compounding process. g scope.

[0083] In one embodiment, certain crystallizable polyester compositions useful in the present disclosure may be visually clear.The term "visually clear" is defined herein as being visibly absent of cloudiness, haziness, and / or muddiness upon visual inspection.

[0084] In one embodiment, the polyester portion of the crystallizable polyester composition useful in the present disclosure can be made by methods known in the literature, such as by a process in a homogeneous solution, by a transesterification process in a melt, and by a two-phase interface process. For methods of producing polyesters, see U.S. Pat. No. 3,772,405, which is incorporated herein by reference for its disclosure of such methods.

[0085] In certain embodiments, as described in more detail in U.S. Pat. No. 2,720,507, which is incorporated herein by reference, the crystallizable polyester composition can be prepared by condensing a dicarboxylic acid or a dicarboxylic acid ester with a diol in an inert atmosphere in the presence of a catalyst at gradually increasing temperatures during the condensation process and then condensing under reduced pressure in the later stages of the condensation.

[0086] In one aspect, the present disclosure is a catalyst system for preparing a polyester composition. In one aspect, the present disclosure is a catalyst system for preparing a polyester composition comprising neopentyl glycol (NPG or 2,2-dimethyl-1,3-propanediol). In one embodiment, the catalyst system of the present disclosure is suitable for polyesters comprising neopentyl glycol (NPG) and / or 1,4-cyclohexanedimethanol (CHDM). In one embodiment, the catalyst system of the present disclosure is also suitable for polyester compositions comprising terephthalic acid, ethylene glycol, diethylene glycol, NPG and CHDM. In one embodiment, this catalyst system is also suitable for polyester compositions that do not contain NPG but comprise terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol. In one embodiment, process improvements can be seen when the titanium content is kept very low and the reaction temperature is increased to a temperature above the temperature range typically used to produce these types of polyester compositions.

[0087] In one aspect, the catalyst system of the present disclosure is a combination of low amounts of titanium and antimony, and the system is effective over a wide range of polymerization temperatures; particularly at higher polymerization temperatures. In one embodiment, phosphorus is optionally used as a catalyst moderator. In certain embodiments, when phosphorus is used, the concentration of the phosphorus compound is determined based on the amount of titanium and antimony used in the catalyst system. In one embodiment, the amount of phosphorus compound used is determined based on the final polymerization temperature.

[0088] In one embodiment, the catalyst system of the present disclosure comprises a titanium compound at a concentration level of 2 to 15 ppm titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 4 to 12 ppm titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 3 to 10 ppm titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 1 to 20 ppm titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 20 ppm or less titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 15 ppm or less titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 14 ppm or less titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 13 ppm or less titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 12 ppm or less titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 10 ppm or less of titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 7 ppm or less of titanium relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises a titanium compound at a concentration level of 5 ppm or less of titanium relative to the weight of the polyester produced. In one embodiment, the titanium compound is a tetraalkyl titanate, such as tetraisopropyl titanate. In one embodiment, the titanium compound is selected from titanium tetraalkoxides, such as titanium tetraisopropoxide, titanium tetraethoxide, or titanium tetrabutoxide; or a tetraalkyl titanate, such as tetraisopropyl titanate, and mixtures thereof.

[0089] In one embodiment, the catalyst system comprises an antimony compound at a concentration level of 50 to 150 ppm antimony relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises an antimony compound at a concentration level of 70 to 140 ppm antimony relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises an antimony compound at a concentration level of 90 to 130 ppm antimony relative to the weight of the polyester produced. In one embodiment, the catalyst system comprises an antimony compound at a concentration level of 100 to 120 ppm antimony relative to the weight of the polyester produced. In one embodiment, the antimony compound is antimony trioxide. In one embodiment, the antimony compound is antimony trioxide, antimony acetate or antimony oxalate. In one embodiment, the antimony compound of the catalyst system is dissolved in one of the diols used in the polyester composition.

[0090] In one embodiment, the concentration level of phosphorus is from 0 to 90 ppm based on the weight of the polyester produced. In one embodiment, the concentration level of phosphorus is from 0 to 50 ppm based on the weight of the polyester produced. In one embodiment, the concentration level of phosphorus is from 2 to 75 ppm based on the weight of the polyester produced. In one embodiment, the concentration level of phosphorus is from 2 to 50 ppm based on the weight of the polyester produced. In one embodiment, the concentration level of phosphorus is from 10 to 60 ppm based on the weight of the polyester produced. In one embodiment, the concentration level of the antimony compound depends on the temperature in the final reaction stage or post-processing zone. In one embodiment, the concentration level of the antimony compound depends on the titanium content used. In one embodiment, the concentration level of the antimony compound depends on the temperature of the final reaction stage and the titanium content used.

[0091] In one aspect of the present disclosure, the polymerization temperature is much higher than in standard copolyester production reactions. In one embodiment, the polymerization temperature is from 275°C to 310°C. In one embodiment, the polymerization temperature is from 285°C to 300°C. In one embodiment, the polymerization temperature is from 290°C to 300°C.

[0092] In one embodiment, the polymerization temperature is 290°C, the titanium concentration is 8 ppm or less and the antimony loading is 125 ppm, and the phosphorus loading is 0 to 8 ppm to produce a high IV polyester with good color. In one embodiment, the polymerization temperature is 300°C, the titanium concentration is 13 ppm or less and the antimony concentration is 100 ppm, and the phosphorus concentration is 59 to 60 ppm to produce a high IV polyester with good color.

[0093] In one embodiment, the catalyst components and the phosphorus source are added after the esterification of terephthalic acid. In one embodiment, the conversion rate of terephthalic acid groups to their ester forms by the one or more diols used is 90%. In one embodiment, a higher conversion rate of up to 100% of the available carboxylic acid ends can be obtained with the catalyst system of the present disclosure. In one embodiment, the catalyst components can be added together or they can be added separately. In another embodiment, phosphorus is added as a separate feed after the catalyst is added.

[0094] In one embodiment, no changes need to be made to the reaction procedures typically used for high titanium-phosphorus systems, other than the option of utilizing higher post-treatment (polymerization) temperatures.

[0095] This catalyst system enables users to prepare NPG-containing polyesters with excellent productivity and good product color relative to pure titanium systems. The flexibility to use high reaction temperatures without negatively affecting color enables the use of temperature as a variable to change productivity. This option is not generally available due to the sensitivity of more conventional titanium catalyst systems to elevated temperatures.

[0096] In one aspect, the polyester compositions of the present disclosure can be produced using any polycondensation reaction conditions known in the art. They can be produced by continuous, semi-continuous and batch operation modes and can utilize various reactor types. Examples of suitable reactor types include, but are not limited to, stirred tanks, continuous stirred tanks, slurry reactors, tubular reactors, wiped film reactors, falling film reactors, or extrusion reactors.

[0097] As used herein, the term "continuous" refers to a process in which the reactants are introduced in an uninterrupted manner and the products are simultaneously withdrawn. For economic reasons, the process is advantageously run as a continuous process and produces a low color polymer, since the appearance of the polyester may deteriorate if allowed to reside in the reactor for too long at elevated temperatures.

[0098] The polyesters of the present disclosure are prepared by any procedure known to those skilled in the art. The reaction of the diol component and the dicarboxylic acid component can be carried out using conventional polyester polymerization conditions. For example, when preparing the polyester by means of an ester exchange reaction, for example, starting from the ester form of the dicarboxylic acid component, the reaction process may include at least two steps.

[0099] In one embodiment of the present disclosure, polyester is manufactured in two main stages. The first stage reacts the raw materials to form monomers and / or oligomers. If the raw materials entering the first stage contain acid end groups, such as TPA or isophthalic acid, the first stage is referred to as esterification. The second stage further reacts the monomers and / or oligomers to form the final polyester product. The second stage is generally referred to as the polycondensation stage. The polycondensation stage can be a single step, or can be divided into a pre-polycondensation (or prepolymerization) step and a final (or post-processing) polycondensation step.

[0100] In the first step, the esterification step, a diol component, such as ethylene glycol, and a dicarboxylic acid component, such as terephthalic acid, are reacted at a temperature of about 150° C. to about 270° C. at a pressure of about 5 to 60 pounds per square inch (“psig” or “psi”) for about 0.5 to about 8 hours. In one embodiment, the temperature for the esterification or transesterification reaction is about 180° C. to about 230° C. for about 1 to about 4 hours, while the pressure is about 103 kPa gauge (15 psig) to about 276 kPa gauge (40 psig). In one embodiment, the temperature for the esterification or transesterification reaction is about 240° C. to about 270° C. for about 1 to about 4 hours, while the pressure is about 5 psig to about 50 psi. Thereafter, the reaction product is heated at a higher temperature and reduced pressure to form a polyester while eliminating the diol, which is readily volatile and removed from the system under these conditions.

[0101] The second step, the prepolymerization or polycondensation step, is carried out under high vacuum and at a temperature of typically about 250° C. to about 275° C., or about 255° C. to about 270° C., or about 260° C. to about 270° C., for about 0.1 to about 6 hours, or about 0.2 to about 2 hours, until a polymer having the desired degree of polymerization as determined by inherent viscosity is obtained. The polycondensation step may be carried out under reduced pressure of about 200 mmHg to 500 mmHg. In one embodiment, the temperature for the prepolymerization or polycondensation reaction is about 240° C. to about 270° C. for about 1 to about 4 hours, while the pressure is about 200 mmHg to about 500 mmHg. Agitation or other appropriate means or conditions are used in both stages to ensure adequate heat transfer and surface renewal of the reaction mixture.

[0102] In certain embodiments, the reaction rates of both stages, esterification and polycondensation, can be increased by the presence of a catalyst. In one embodiment, the catalyst is added to the esterification reaction. In one embodiment, the catalyst is added to the polycondensation reaction. In one embodiment, the titanium compound and the antimony compound are added together, and the phosphorus compound is added as a separate feed after the catalyst is added. In one embodiment, the titanium compound, antimony compound, and phosphorus compound are added after the esterification of terephthalic acid.

[0103] In one embodiment, there is a post-treatment or final polycondensation step. In this step, the reaction continues until the desired IV is reached. In one aspect of the disclosure, this final post-treatment step is at a higher elevated temperature (compared to pure titanium catalyst systems). In one embodiment, useful post-treatment temperatures are 280 to 310°C or 285 to 300°C. Elevated post-treatment temperatures can produce high IV polyesters with good color.

[0104] In one embodiment, the present disclosure is a method of post-treating a polycondensation product to make a polyester, wherein the polyester has an inherent viscosity of at least 0.50 g / dL or 0.50-0.90 g / dL, and wherein the post-treatment polymerization temperature is elevated from 280 to 320° C. and the pressure is from 0.3 to 7 mmHg.

[0105] For example, one embodiment of the present disclosure is a method for preparing a crystallizable reactor-grade polyester composition, comprising: reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues, and ethylene glycol residues in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound to produce an esterification product; wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; prepolymerizing the esterification product in the presence of 0 to 90 ppm of a phosphorus compound to produce a polycondensation product, wherein the prepolymerization temperature is 255 to 275° C. and the pressure is 200-500 mmHg; post-treating the polycondensation product to produce a polyester, wherein the polyester has an inherent viscosity of at least 0.50 g / dL or 0.50-0.90 g / dL, and wherein the post-treatment polymerization temperature is elevated to 280-320° C. and the pressure is 0.3 to 7 mmHg.

[0106] Another embodiment is a method of preparing a crystallizable reactor-grade polyester composition, comprising: reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues, and ethylene glycol residues to produce an esterification product, wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; prepolymerizing the esterification product in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound, and 0 to 90 ppm of a phosphorus compound to produce a prepolymerized polycondensation product, wherein the polycondensation temperature is 255 to 275° C.; and post-treating the polycondensation product to produce a polyester, wherein the polyester has an inherent viscosity of at least 0.50 dL / g or 0.50-0.90 dL / g, and wherein the post-treatment polymerization temperature is elevated to 280 to 320° C. and the pressure is 0.3 to 7 mmHg.

[0107] In order to ensure that the reaction of the diol component and the dicarboxylic acid component by the transesterification reaction is driven to completion, it is sometimes necessary to use an excess of about 1.05 to about 2.5 moles of the diol component relative to 1 mole of the dicarboxylic acid component. However, those skilled in the art will understand that the ratio of the diol component to the dicarboxylic acid component generally depends on the design of the reactor in which the reaction process is carried out.

[0108] In some embodiments, suitable glycols include, but are not limited to, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, polyethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, p-xylene glycol, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethylcyclobutane-1,3-diol, polytetramethylene glycol, isosorbide, or mixtures thereof.

[0109] In one embodiment, copolyesters suitable for use in the present disclosure are prepared from monomers such as dimethyl terephthalate (DMT), terephthalic acid (TPA), isophthalic acid (IPA), 1,4-cyclohexanedicarboxylic acid (CHDA), ethylene glycol (EG), diethylene glycol (DEG), neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), and 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD).

[0110] According to the present disclosure, a method of preparing a polyester product is provided.

[0111] In one embodiment, the reaction zone can be a single vessel, which is typically a continuous stirred tank reactor (CSTR), which can be an integrated unit with multiple esterification zones and appropriate separation and control. Likewise, although the reaction zone can be a single vessel, which is typically a wiped film or thin film type CSTR, these vessels can be combined in one or more integrated units with multiple polycondensation zones and appropriate separation and control. Various other types of esterification and polycondensation reactors and reactor arrangements are known in the art and can be suitable for use in accordance with the present disclosure.

[0112] In one embodiment, a paste consisting of EG and TPA in a 2:1 molar ratio is fed to a paste tank. In one embodiment, additional EG is fed to the first reaction zone or reactor 1 and other diols such as CHDM, TMCD, NPG and DEG are also fed to the first reaction zone at the same location. In one embodiment, these monomers can be separated and / or added directly to the first reaction zone.

[0113] In one embodiment, the reaction mixture is heated in the first reaction zone by means of a recirculation loop comprising a heat exchanger. Esterification occurs in the first reaction zone to form a first esterification product comprising copolyester monomers, oligomers or both and unreacted TPA, EG and other glycols, such as CHDM, TMCD, NPG or DEG. The reaction product of the first reaction zone is then transferred to the second reaction zone. Further esterification occurs in the second reaction zone to form a second esterification product comprising additional polyester monomers, oligomers or both. In certain embodiments, the average chain length of the monomers and / or oligomers leaving the esterification stage may be less than 25, 1 to 20, or 5 to 15.

[0114] In some embodiments, the reaction product of the second reaction zone is then transferred to a third reaction zone to form a prepolymer product comprising a copolyester oligomer. In some embodiments, the third reaction zone converts the monomers leaving the esterification stage into oligomers having an average chain length of 2 to 40, 5 to 35, or 10 to 30.

[0115] The prepolymer product is then conveyed to one or more final reaction zones or post-processing zones. Additional polycondensation occurs in the post-processing zones to form a copolyester having a desired average chain length or IV. The copolyester is then removed from the post-processing zones for subsequent processing, such as forming into pellets by an extruder connected to an underwater pelletizer.

[0116] In one embodiment, the average residence time of the reactants in the reaction step is 2 hours or less, 1.75 hours or less, 1.5 hours or less, 1.25 hours or less, 1 hour or less, or 0.75 hour or less. In various embodiments, the average residence time of the reactants in the reaction step is 30 to 40 minutes.

[0117] In one embodiment, the average residence time of the reactants in the esterification step is 2 hours or less, 1.75 hours or less, 1.5 hours or less, 1.25 hours or less, 1 hour or less, or 0.75 hours or less. In various embodiments, the average residence time of the reactants in the esterification step (d) is 30 to 40 minutes.

[0118] In various embodiments, the total molar ratio of EG:TPA introduced into the process is from 2.3:1 to 3.0:1.

[0119] In various embodiments, the total molar ratio of EG:TPA introduced into the process is from 2.3:1 to 2.71:1.

[0120] The catalysts may be added during the esterification stage or the polycondensation stage. In one embodiment, they are added with the feed to the first reaction zone.

[0121] In some embodiments, phosphorus compounds are usually added with catalysts to improve thermal stability. Phosphorus compounds that can be used as heat stabilizers include phosphoric acid, phosphorous acid, phosphonic acid, phosphinic acid, phosphous acid and their various esters and salts. The ester can be an alkyl, branched alkyl, substituted alkyl, difunctional alkyl, alkyl ether, aryl and substituted aryl. In some embodiments, suitable heat stabilizers include triphenyl phosphate. In one embodiment, phosphorus is added in the range of 0 to 90 ppm based on the weight of the copolyester.

[0122] In various embodiments, one or more other additives may be added to the raw materials, copolyesters and / or copolyester monomers / oligomers at one or more locations within the process. In various embodiments, suitable additives may include, for example, trifunctional or tetrafunctional comonomers such as trimellitic anhydride, trimethylolpropane, pyromellitic dianhydride, pentaerythritol or other polyacids or polyols; crosslinking agents or other branching agents; colorants; toners; pigments; carbon black; glass fibers; fillers; impact modifiers; antioxidants; UV absorber compounds; oxygen scavenging compounds; etc.

[0123] The processes according to the present disclosure are particularly suitable for use on an industrial scale. For example, they can be implemented on a commercial production line capable of operating at a rate of 500 to 30,000 lbs / hr polymer.

[0124] In another aspect, the present disclosure relates to copolyesters made by the process of the present disclosure.

[0125] In some embodiments, in the process of making the polyester that can be used for the present disclosure, certain reagents that color the polymer, including toners or dyes, can be added to the melt. In one embodiment, a bluing toner is added to the melt to reduce the b* of the resulting polyester polymer melt phase product. Such bluing agents include one or more blue inorganic and organic toners and / or dyes. In addition, one or more red toners and / or dyes can also be used to adjust the a* color. One or more organic toners can be used, such as one or more blue and red organic toners, such as one or more toners described in U.S. Patents 5,372,864 and 5,384,377, which are incorporated herein by reference in their entirety. One or more organic toners can be fed as a premixed composition. The premixed composition can be a pure blend of red and blue compounds, or the composition can be pre-dissolved or pulped in one of the raw materials of the polyester, such as ethylene glycol.

[0126] The total amount of toner components added may depend on the amount of yellow inherent in the base polyester and the effectiveness of the toner. In one embodiment, a total organic toner component concentration of up to about 15 ppm may be used, and a minimum concentration of about 0.5 ppm. In one embodiment, the total amount of bluing additives may be 0.5 to 10 ppm. In one embodiment, one or more toners may be added to the esterification zone or the polycondensation zone. Preferably, one or more toners are added to the esterification zone or to the early stages of the polycondensation zone, such as in a prepolymer reactor.

[0127] In embodiments, the polyester composition may also contain from 0.01 to 25% by weight of common additives based on the total composition, such as release agents, anti-slip agents, anti-blocking agents, flame retardants, plasticizers, glass bubbles, nucleating agents, stabilizers, including but not limited to UV stabilizers, heat stabilizers and / or their reaction products, fillers and impact modifiers. Examples of commercially available impact modifiers include but are not limited to ethylene / propylene terpolymers, functionalized polyolefins, such as those containing methyl acrylate and / or glycidyl methacrylate, styrene-based block copolymer impact modifiers, and various acrylic core-shell impact modifiers. Residues of these additives are also expected to be part of the polyester composition.

[0128] In one embodiment, the crystallizable compositions of the present disclosure are used to make films and sheets, including heat shrinkable films and one or more thermoformable sheets. Heat shrinkable plastic films are used as covers to hold objects together, and as outer packaging for bottles, cans, and other types of containers. For example, such films are used to cover the cap, neck, shoulder, or ridge of a bottle or the entire bottle; for labeling, protecting, wrapping, or adding value to a product; and for other reasons. In addition, such films can be used as covers to package objects such as boxes, bottles, boards, rods, or notebooks together in groups, and such films can also be closely attached as packaging materials. The above uses take advantage of the shrinkability and internal shrinkage stress of the film.

[0129] In the past, poly(vinyl chloride) (PVC) films dominated the shrink film market. However, polyester films have become an important alternative because polyester films do not have the environmental issues associated with PVC films. Polyester shrink films ideally have properties very similar to PVC films so that polyester films can serve as a "drop-in" replacement film and can be processed in existing shrink tunnel equipment. The properties of PVC films that are desired to be replicated include the following: (1) a relatively low shrink initiation temperature, (2) a total shrinkage that increases gradually and in a controlled manner with increasing temperature, (3) a low shrink force to prevent crushing of the underlying container, (4) a high total shrinkage (e.g., 50% or greater), and (5) inherent film toughness to prevent unwanted tearing and splitting of the film before and after shrinking.

[0130] Heat shrinkable films must meet various suitability criteria to be used in this application. The film must be strong, must shrink in a controlled manner, and must provide sufficient shrinkage force to hold itself to the bottle without crushing the contents. In addition, when these labels are applied to polyester containers, they must not interfere with the recycling process of the PET bottles. In fact, it would be advantageous if the label were also recyclable so that the entire container could be recycled and converted into new products without incurring additional handling requirements or creating new environmental problems. Heat shrinkable films are made from a variety of raw materials to meet a range of material requirements. The present disclosure describes unique and unexpected effects measured with certain monomer combinations that improve the recyclability of polyester shrink film labels.

[0131] Polyester shrink film compositions are used commercially as shrink film labels for food, beverages, personal care, household products, etc. Typically, these shrink films are used in combination with clear polyethylene terephthalate (PET) bottles or containers. The entire package (bottle plus label) is then put into the recycling process. At a typical recycling center, the PET and shrink film materials usually end up together at the end of the process due to the similarity in composition and density. The PET bottle flakes need to be dried to remove residual water that is left in the PET through the recycling process. Typically, during the recycling process, the PET is dried at temperatures above 200°C. At these temperatures, typical polyester shrink film resins soften and become sticky, often forming clumps with the PET bottle flakes. These clumps must be removed before further processing. These clumps reduce the yield of PET bottle flakes from the process and result in additional handling steps.

[0132] In embodiments of the present disclosure, certain oriented films and / or shrinkable films comprising the polyesters and / or polyester compositions useful in the present disclosure may have a unique combination of all of the following properties: good stretchability, controlled shrinkage properties, certain toughness, certain inherent viscosity, certain glass transition temperature (T g ), a certain strain induced crystallization melting point, a certain flexural modulus, a certain density, a certain tensile modulus, a certain surface tension, good melt viscosity, good clarity and good color.

[0133] In one embodiment, films and shrink films according to the present disclosure may contain 0.01 to 10 wt % polyester plasticizers, such as those described in US Pat. No. 10,329,393, which is incorporated herein by reference. In one embodiment, the shrink film may contain 0.1 to 5 wt % polyester plasticizers.

[0134] In one aspect, the present disclosure relates to one or more shrink films, extruded sheets, thermoformed articles, and one or more molded articles comprising the crystallizable polyester composition of the present disclosure. Methods of forming the polyester composition into one or more films and / or sheets are well known in the art. Examples of one or more sheets that can be used in the present disclosure include, but are not limited to, one or more extruded sheets, one or more compression molded films, one or more calendered films and / or sheets, and one or more solution cast films and / or sheets. In one aspect, methods of making films and / or sheets that can be used to make the shrink film of the present disclosure include, but are not limited to, extrusion, compression molding, calendering, and solution casting.

[0135] In one embodiment, the polyester compositions useful in the present disclosure are made into films using any method known in the art for producing films from polyesters, such as solution casting, extrusion, compression molding, or calendaring (see, e.g., U.S. Pat. Nos. 6,846,440; 6,551,699; 6,551,688; and 6,068,910, incorporated herein by reference).

[0136] In one embodiment, the as-formed film is subsequently oriented in one or more directions (e.g., uniaxially and / or biaxially oriented films). Such orientation of the film can be performed by any method known in the art using standard orientation conditions. In one embodiment, the oriented film of the present disclosure can be made from a film having a thickness of about 100 to 400 microns, such as an extruded, cast, or calendered film, which can be formed at T g To T g +55°C or 70°C to 125°C at a ratio of 5:1 to 3:1, for example, 5:1 or 3:1 at a temperature of 70°C to 100°C, and can be oriented to a thickness of 20 to 80 microns. In one embodiment, the orientation of the initial pre-shrink film can be carried out on a tenter according to these orientation conditions. The shrink film of the present disclosure can be made from the oriented film of the present invention.

[0137] In one embodiment, the shrink film of the present disclosure may have a shrink initiation temperature of about 55 to about 80° C., or about 55 to about 75° C., or about 55 to about 70° C. The shrink initiation temperature is the temperature at which shrinkage begins to occur.

[0138] In certain embodiments, the polyester compositions useful in the present disclosure may have a density of 1.6 g / cc or less, or 1.5 g / cc or less, or 1.4 g / cc or less, or 1.1 g / cc to 1.5 g / cc, or 1.2 g / cc to 1.4 g / cc, or 1.2 g / cc to 1.35 g / cc.

[0139] In one embodiment, the density of the film is reduced by introducing many small voids or holes in the film or shaped article. This method is called "voiding", which may also be referred to as "cavitating" or "microvoiding". The voids are obtained by incorporating about 1 to about 50% by weight of small organic or inorganic particles (including glass microspheres) or "inclusions" (referred to in the art as "voiding" or "cavitating" agents) into the matrix polymer and stretching the polymer in at least one direction to orient the polymer. During the stretching process, small holes or voids are formed around the voiding agent. When voids are introduced into the polymer film, the resulting void-containing film not only has a lower density than a void-free film, but also becomes opaque and forms a paper-like surface. This surface also has the advantage of improved printability; that is, the surface can accept many inks with a significantly higher capacity than a void-free film. Typical examples of void-containing films are described in U.S. Patents 3,426,754; 3,944,699; 4,138,459; 4,582,752; 4,632,869; 4,770,931; 5,176,954; 5,435,955; 5,843,578; 6,004,664; 6,287,680; 6,500,533; 6,720,085; U.S. Patent Application Publication Nos. 2001 / 0036545; 2003 / 0068453; 2003 / 0165671; 2003 / 0170427; Japanese Patent Application Nos. 61-037827; 63-193822; 2004-181863; European Patent No. 0 581 970 B1 and European patent application 0 214 859 A2.

[0140] In certain embodiments, the film so extruded is oriented while being stretched. Oriented films or shrinkable films of the present disclosure can be made of films with any thickness, depending on the desired end use. In one embodiment, the ideal condition is that the oriented films and / or shrinkable films can be printed with inks for use in applications including labels, photographic films that can be attached to substrates such as paper, and / or can be used for shrinking to surround other applications outside of bottles or containers. It may be desirable to coextrude polyesters that can be used for the present disclosure with another polymer, such as PET, to make films that can be used for making oriented films and / or shrink films of the present disclosure. An advantage of the latter approach is that a bonding layer may not be required in some embodiments.

[0141] In certain embodiments, the shrink films of the present disclosure shrink gradually with little to no wrinkling. In certain embodiments, the shrink films of the present disclosure have a transverse direction shrinkage of no greater than 40% per 5°C temperature increment.

[0142] In certain embodiments of the present disclosure, when immersed in 65°C water for 10 seconds, the shrink film of the present disclosure has a longitudinal shrinkage of 10% or less, or 5% or less, or 3% or less, or 2% or less, or no shrinkage. In certain embodiments of the present disclosure, when immersed in 65°C water for 10 seconds, the shrink film of the present disclosure has a longitudinal shrinkage of -10% to 10%, -5% to 5%, or -5% to 3%, or -5% to 2%, or -4% to 4%, or -3% to 4%, or -2% to 4%, or -2% to 2.5%, or -2% to 2%, or 0 to 2%, or no shrinkage. Negative longitudinal shrinkage percentages refer to longitudinal growth here. Positive longitudinal shrinkage refers to longitudinal shrinkage.

[0143] In certain embodiments of the present disclosure, the shrink film of the present disclosure has a shrinkage in a main shrinking direction of 50% or more, or 60% or more, or 70% or more when immersed in 95° C. water for 10 seconds.

[0144] In certain embodiments of the present disclosure, the shrink film of the present disclosure has a shrinkage in the main shrinkage direction in an amount of 50 to 90% and a longitudinal shrinkage of 10% or less, or -10% to 10%, when immersed in 95°C water for 10 seconds.

[0145] In one embodiment, the polyester useful in the present disclosure is formed into a film using any method known in the art for producing films from polyesters, such as solution casting, extrusion, compression molding, or calendaring. The film so extruded (or so formed) is then oriented in one or more directions (e.g., a uniaxially and / or biaxially oriented film). Such orientation of the film can be performed by any method known in the art using standard orientation conditions. For example, the uniaxially oriented film of the present disclosure can be made from a film having a thickness of about 100 to 400 microns, such as an extruded, cast, or calendared film, which can be formed at the T of the film. g To T g It is stretched at a temperature of +55°C at a ratio of 6.5:1 to 3:1 and can be stretched to a thickness of 20 to 80 microns. In one embodiment, the initial as-extruded film orientation can be carried out on a tenter frame according to these orientation conditions.

[0146] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrink initiation temperature of about 55 to about 80° C., or about 55 to about 75° C., or 55 to about 70° C. The shrink initiation temperature is the temperature at which shrinkage begins to occur or the shrinkable film begins to shrink.

[0147] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrinkage initiation temperature of 55°C to 70°C.

[0148] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a percent strain at break greater than 200% at a stretching speed of 500 mm / min in a direction perpendicular to the primary shrinking direction according to ASTM method D882.

[0149] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a percent strain at break greater than 300% at a stretching speed of 500 mm / min in a direction perpendicular to the primary shrinking direction according to ASTM method D882.

[0150] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a tensile stress at break (break stress) of 20 to 400 MPa; or 40 to 260 MPa; or 42 to 260 MPa as measured according to ASTM method D882.

[0151] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrink force of 4 to 18 MPa, or 4 to 15 MPa, depending on the stretching conditions and the desired end use, as measured by ISO Method 14616. For example, certain labels made for plastic bottles may have a shrink force of 4 to 8 MPa, and certain labels made for glass bottles may have a shrink force of 10 to 14 MPa as measured by ISO Method 14616 using a LabThink FST-02 Thermal Shrinkage Tester and reported in MPa.

[0152] In one embodiment of the present disclosure, the polyester composition may be formed by reacting monomers in a known process for making polyesters, which is generally referred to as a reactor grade composition.

[0153] Molded articles, which may or may not consist of or contain a shrink film, may also be made from any of the polyester compositions disclosed herein and are included within the scope of the present disclosure.

[0154] In one embodiment, when having a pre-orientation thickness of about 100 to 400 microns, the printed film is subsequently stretched on a tenter frame at T g To T gWhen oriented at a temperature of +55°C at a ratio of 6.5:1 to 3:1 to a thickness of about 20 to about 80 microns, the shrink films of the present disclosure may have one or more of the following properties: (1) a shrinkage in the primary shrinkage direction or transverse direction of greater than 60% (or greater than 70%), and a shrinkage in the machine direction of 10% or less (or -5% to 4%) when immersed in 95°C water for 10 seconds; (2) a shrinkage initiation temperature of about 55°C to about 70°C; (3) a percent strain at break of greater than 200%, or 200 to 600%, or 200 to 500%, or 226 to 449%, or 250 to 455% at a stretching speed of 500 mm / min in the transverse direction or in the machine direction or in both directions according to ASTM method D882; (4) a shrinkage of no more than 40% per 5°C temperature increment; and / or (5) a strain-induced crystalline melting point of greater than or equal to 200°C. Any combination of these properties or all of these properties may be present in the shrink film of the present disclosure. The shrink film of the present disclosure may have a combination of two or more of the above shrink film properties. The shrink film of the present disclosure may have a combination of three or more of the above shrink film properties. The shrink film of the present disclosure may have a combination of four or more of the above shrink film properties. In certain embodiments, properties (1)-(2) are present. In certain embodiments, properties (1)-(5) are present. In certain embodiments, properties (1)-(3) are present, and so on.

[0155] The shrinkage percentages in this article are based on the shrinkage percentages that have been measured on a tenter frame at T g To T g An initially so formed film having a thickness of about 20 to 80 microns oriented at a temperature of 6.5:1 to 3:1 at a temperature of +55°C, for example, oriented at a ratio of 5:1 at a temperature of 70°C to 85°C. In one embodiment, the shrink properties of the oriented film used to make the shrink film of the present disclosure are not adjusted by annealing the film at a temperature above its orientation temperature.

[0156] The shape of the film that can be used to make the oriented film or shrink film of the present disclosure is not limited in any way. For example, it can be a flat film or a film that has been formed into a tube. The film formed into a tube can use a bonding solvent or a bonding adhesive to bond or combine the edges of the film together during the shrinking process. In order to produce the shrink film that can be used in the present disclosure, the polyester is first formed into a flat film and then "uniaxially stretched", which means that the polyester film is oriented in one direction and the edges of the stretched film are bonded to form a tube or sleeve using a bonding solvent or a bonding adhesive. The film can also be "biaxially oriented", which means that the polyester film is oriented in two different directions; for example, the film is stretched in the longitudinal direction and in a direction different from the longitudinal direction. Usually, but not always, the two directions are substantially perpendicular. For example, in one embodiment, the two directions are the longitudinal or machine direction ("MD") of the film (the direction in which the film is produced on the film making machine) and the transverse direction ("TD") of the film (the direction perpendicular to the MD of the film). The biaxially oriented film can be sequentially oriented, simultaneously oriented, or oriented by some combination of simultaneous and sequential stretching.

[0157] The film can be oriented by any common method, such as roller stretching, long gap stretching, tenter stretching and tubular stretching. By using any of these methods, it is possible to carry out sequential biaxial stretching, simultaneous biaxial stretching, uniaxial stretching or a combination of these. For the biaxial stretching mentioned above, longitudinal and transverse stretching can be carried out simultaneously. Stretching can also be carried out first in one direction and then in the other direction to produce effective biaxial stretching. In one embodiment, by preheating the film to a temperature higher than its glass transition temperature (T g ) is 5°C to 80°C higher than its T g 5°C to 30°C higher. In one embodiment, the stretching rate is 0.5 to 20 inches (1.27 to 50.8 cm) / second. The film can then be oriented, for example, in the machine direction, the transverse direction, or both directions, 2 to 6 times the original measurement. The film can be oriented as a single layer film, or can be coextruded with another polyester, such as PET (polyethylene terephthalate) as a multilayer film and then oriented.

[0158] In one embodiment, the present disclosure includes an article or shaped article comprising a shrink film of any shrink film embodiment of the present disclosure. In another embodiment, the present disclosure includes an article or shaped article comprising an oriented film of any oriented film embodiment of the present disclosure.

[0159] In certain embodiments, the present disclosure includes, but is not limited to, shrink films applied to containers, plastic bottles, glass bottles, packaging, batteries, hot-fill containers, and / or industrial articles or other applications. In one embodiment, the present disclosure includes, but is not limited to, oriented films applied to containers, packaging, plastic bottles, glass bottles, photo substrates such as paper, batteries, hot-fill containers, and / or industrial articles or other applications.

[0160] In certain embodiments of the present disclosure, the shrink film of the present disclosure can be formed into a label or sleeve. The label or sleeve can then be applied to an article, such as a container wall, a battery pack, or applied to a sheet or film.

[0161] The oriented films or shrink films of the present disclosure can be applied to shaped articles, such as tubes or bottles, and are commonly used in various packaging applications. For example, films and sheets made from polymers such as polyolefins, polystyrene, poly(vinyl chloride), polyesters, polylactic acid (PLA), etc. are often used to make shrink labels for plastic beverage or food containers. For example, the shrink films of the present disclosure can be used in many packaging applications, where the shrink films applied to the shaped articles exhibit properties such as good printability, good shrink force, good texture, high shrinkage, controlled shrinkage rate, good stiffness, and recyclability.

[0162] Improved shrink properties and recyclability provide new business options including, but not limited to, shrink films applied to containers, plastic bottles, glass bottles, packaging, battery packs, hot fill containers and / or industrial articles or other applications.

[0163] In one aspect of the present disclosure, the disclosed polyester compositions can be used as one or more thermoformed and / or thermoformable sheets. The present disclosure also relates to articles comprising one or more thermoformed sheets of the present disclosure. In one embodiment, the polyester compositions of the present disclosure can be used as one or more sheets that are easily formed into shaped articles or parts or molded articles or parts. In one embodiment, one or more films and / or one or more sheets of the present disclosure can be processed into molded articles or parts by thermoforming. The polyester compositions of the present disclosure can be used in various molding and extrusion applications.

[0164] In addition, in one embodiment, the polyester composition useful for one or more thermoformable sheets of the present disclosure may also contain 0.1 to 25 weight percent of the total composition of commonly used additives such as colorants, antiblocking agents, slip agents, mold release agents, flame retardants, plasticizers, nucleating agents, stabilizers, including but not limited to UV stabilizers, heat stabilizers, fillers, and impact modifiers.

[0165] In one embodiment, reinforcing materials may be included in one or more thermoformed sheets comprising the polyester composition of the present disclosure. For example, suitable reinforcing materials may include carbon filaments, silicates, mica, clay, talc, titanium dioxide, wollastonite, glass flakes, glass beads and fibers and polymeric fibers and combinations thereof.

[0166] In one embodiment, the one or more thermoformed sheets of the present disclosure are one or more multi-layer sheets. In one embodiment, at least one layer of the multi-layer sheet is a foam or expanded polymer or polyester layer.

[0167] One aspect of the present disclosure is a method of making molded or formed parts and articles using thermoforming.Any thermoforming technique or method known to those skilled in the art can be used to produce the molded or formed articles and parts of the present disclosure.

[0168] In one embodiment, the thermoforming process can be performed in several ways, such as taught in "Technology of Thermoforming"; Throne, James; Hanser Publishers; 1996; pages 16-29, which is incorporated herein by reference. In some embodiments, it is a positive thermoforming process, in which gas or air pressure is applied to the softened sheet, and the sheet is then stretched and drawn out like a bubble, and a male mold is introduced into the bubble from the inside. A vacuum is then applied to cause the part to be further drawn and follow the male mold surface. In this thermoforming process, biaxial stretching / orientation is primarily accomplished in one step as gas or air pressure is applied to the softened sheet. The sheet is then cooled to below the T of the sheet. g The molding step is completed by fixing the orientation into the sheet with the help of vacuum and positive mold to achieve a good balance of physical and appearance properties. In other embodiments, it is a negative thermoforming process, in which vacuum or physical plug is applied to the heat softened sheet and the sheet is stretched and pulled to near the final part size, and then positive air pressure from the inside or further external vacuum from the outside pulls the sheet and makes the sheet follow the external negative mold, and as it cools to below the T of the sheet, the sheet is g The orientation is fixed and the sheet is formed into an article.

[0169] In some embodiments, the bubbles generated are further shaped, sometimes with the aid of a plunger, after which the sheet is draped over the raised male mold and shaped, and then corners and shelf guides, etc., are pulled into the mold by applying a vacuum. In some embodiments, the molded parts or articles may be trimmed, punched, and chamfered as desired after removal from the mold.

[0170] In other embodiments, thermoforming is a process in which a sheet of the polyester composition of the present disclosure is heated to a temperature sufficient to deform it, and then the heated sheet is made to follow the contours of a mold by means such as vacuum assistance, air pressure assistance, and matched mold assistance. In another embodiment, the heated sheet is placed in a mold and forced to follow the contours of the mold by, for example, applying air pressure, applying a vacuum, plunger assistance, or applying a matched mold. In some embodiments, thermoforming produces thin-walled articles. In some embodiments, thermoforming produces thick-walled articles.

[0171] In one embodiment, the thermoforming method molds the sheet into a desired shape by pressing a male mold into the heated sheet. In certain embodiments, thermoforming involves supporting the male mold of the product between surfaces or countertops equipped with a vacuum. In these embodiments, the heat from an external heat source, such as a hot air blower, a heat lamp or other radiant heat source, is directed to the sheet. In these embodiments, the sheet is heated to a softening point. In these embodiments, a vacuum is then applied to the countertop and below the countertop and around the mold, and the heat-softened sheet is pulled toward the countertop, so that the softened sheet is contacted with the mold surface. In these embodiments, the vacuum pulls the softened sheet to close contact and follows the contour of the mold surface. Therefore, the sheet then presents the shape of the mold. In these embodiments, after the sheet cools, it hardens, and the resulting product or parts can be taken out from the mold.

[0172] In one embodiment, the thermoforming process comprises: forming a sheet from the polyester composition of the present disclosure; heating the sheet until it softens and positioning it over a mold; drawing the preheated sheet onto the heated mold surface; cooling the sheet; and then removing the molded article or part from the mold cavity, or optionally, heat setting the formed sheet by maintaining the sheet in contact with the heated mold for a time sufficient to partially crystallize the sheet.

[0173] In one embodiment, the thermoforming process comprises: forming a sheet from the polyester composition of the present disclosure; heating the sheet to a temperature of about 100°C above the T of the polyester; g or above; applying gas, vacuum and / or physical pressure to the heat softened sheet and stretching the sheet to a shape close to the final part; causing the sheet to conform to the mold shape by vacuum or pressure; cooling the sheet to a temperature below the T of the polyester g and then removing the thermoformed article or part from the mold.

[0174] The sheet for thermoforming can be made by any conventional method known to those skilled in the art. In one embodiment, the sheet is formed by extrusion. In one embodiment, the sheet is formed by calendaring. In one embodiment, during the thermoforming process, the sheet is heated to a temperature of about 100°C. gIn one embodiment, the temperature is higher than the T of the polyester. g In one embodiment, in order to achieve a shorter molding time, heating of the sheet prior to positioning over the thermoforming mold is necessary. In one embodiment, the sheet must be heated to above its T g and below a temperature that would cause it to sag excessively during positioning over the mold cavity. In one embodiment, the molded sheet is cooled to below the T of the polyester prior to removal from the mold. g In one embodiment, the thermoforming process may include vacuum assistance, air assistance, mechanical plunger assistance, or matching molds. In some embodiments, the mold is heated to the T of the sheet. g The selection of the optimum mold temperature depends on the type of thermoforming equipment, the configuration and wall thickness of the molded article, and other factors.

[0175] In some embodiments, the heated sheet is stretched by establishing and drawing a vacuum.

[0176] In one embodiment, heat setting is a process of heat-inducing partial crystallization of a polyester sheet without significant orientation. In one embodiment, heat setting is achieved by maintaining the sheet in contact with a heated mold surface for a sufficient time to achieve a level of crystallinity that provides adequate physical properties for the finished part. In certain embodiments, the level of crystallinity (relative crystallinity) should be greater than about 8 cal / g.

[0177] In one embodiment, the heat-set part can be removed from the mold cavity by known removal means. For example, in one embodiment, backblowing is used and involves breaking the vacuum established between the mold and the formed sheet by introducing compressed air. In some embodiments, the molded article or part is then trimmed, the waste is ground and recycled.

[0178] In some embodiments, the addition of nucleating agents provides faster crystallization during the thermoforming process, and therefore provides faster molding. In one embodiment, nucleating agents such as fine-grained inorganic or organic materials can be used. For example, in one embodiment, suitable nucleating agents include talc, titanium dioxide, calcium carbonate, and immiscible or cross-linked polymers. In one embodiment, the amount of nucleating agent is about 0.01% to about 20% of the weight of the article. In one embodiment, other conventional additives such as pigments, dyes, plasticizers, anti-cracking agents, and stabilizers can be used according to the needs of thermoforming. In some embodiments, anti-cracking agents improve impact strength, and nucleating agents provide faster crystallization. In some embodiments, crystallization is necessary to achieve high temperature stability.

[0179] In one embodiment, the foamed polyester sheet is manufactured by foaming the polyester composition of the present disclosure with a chemical and / or physical foaming agent, extruding the foamed polyester into a sheet, and thermoforming the foamed polyester sheet. Additives for providing enhanced properties to the foamed polyester sheet can be added to the polyester before foaming. Some examples of additives include slip agents, anti-blocking agents, plasticizers, fluorescent whitening agents, and ultraviolet inhibitors. In one embodiment, the foamed polyester sheet can be extruded or laminated on one or both sides using conventional techniques to enhance its properties. In one embodiment, the coating material can be a printed surface providing a product label, rather than the foamed sheet itself.

[0180] In certain embodiments, the compositions of the present disclosure can be used as molded or formed plastic parts or as solid plastic objects. In some embodiments, the compositions of the present disclosure can be used as thermoformed parts or products. In some embodiments, the compositions of the present disclosure are applicable to any application requiring clear hard plastics. In some embodiments, for example, the compositions of the present disclosure are suitable for use as parts such as disposable knives, forks, spoons, plates, cups, straws and eyeglass frames, toothbrush handles, toys, car decorations, tool handles, camera parts, parts of electronic devices, razor parts, ink pen holders, disposable syringes, bottles and the like. In one embodiment, the compositions of the present disclosure can be used as plastics, films, fibers and sheets.

[0181] In one embodiment, the composition can be used as a plastic for making bottles, bottle caps, eyeglass frames, cutlery, disposable cutlery, cutlery handles, shelves, shelf dividers, electronic housings, electronic equipment housings, computer monitors, printers, keyboards, pipes, automotive parts, automotive interiors, automotive decoration, signs, thermoformed letters, siding, toys, thermally conductive plastics, ophthalmic lenses, tools, tool handles, and utensils. In another embodiment, the composition of the present disclosure is suitable for use as a film, sheet, fiber, molded article, molded article, molded part, molded part, medical device, dental tray, dental appliance, container, food container, shipping container, packaging, bottle, bottle cap, eyeglass frames, cutlery, disposable cutlery, cutlery handles, shelves, shelf dividers, furniture components, electronic housings, electronic equipment housings, computer monitors, printers, keyboards, pipes, toothbrush handles, automotive parts, automotive interiors, automotive decoration, signs, outdoor signs, skylights, multi-wall films, multi-layer films, insulation parts, insulation articles, insulation containers, thermoformed letters, siding, toys, toys furniture parts, trays, food trays, dental trays, thermally conductive plastics, ophthalmic lenses and frames, tools, tool handles and utensils, health care products, commercial food service products, boxes, films for graphic arts applications, plastic films for plastic glass laminates, point-of-sale displays, skylights, smoke vents, laminated cards, fenestration, glazing, partitions, ceilings, lighting, machine guards, graphic arts, lenses, extruded laminated sheets or films, decorative laminates, office furniture, face masks, medical packaging, sign holders and shelf price holds on point-of-sale shelves.

[0182] The present thermoformed or thermoformable sheet can be used to form films, molded articles, molded parts, shaped articles, formed parts and sheets. The method of making the thermoformed or thermoformable composition into films, molded articles, molded parts, shaped articles, formed parts and sheets can be according to any method known in the art. Examples of molded articles include, but are not limited to: medical device packaging, medical packaging, health care product packaging, commercial food service products, such as trays, containers, food trays, tumblers, storage boxes, bottles, food processors, blenders and mixer bowls, utensils, water bottles, crisper trays, washing machine parts, refrigerator parts, vacuum cleaner parts, ophthalmic lenses and frames and toys.

[0183] The present disclosure further relates to articles comprising one or more sheets comprising the polyester composition described herein.In embodiments, one or more sheets of the present disclosure may be any thickness desired for the intended application.

[0184] The present disclosure further relates to one or more sheets described herein. The method of forming the polyester composition into one or more sheets includes any method known in the art. Examples of one or more sheets of the present disclosure include, but are not limited to, one or more extruded sheets, one or more calendered sheets, one or more compression molded sheets, and one or more solution cast sheets. The method of making the sheet of the present disclosure includes, but is not limited to, extrusion, calendering, compression molding, wet block processing, dryblock processing, and solution casting.

[0185] The present disclosure further relates to molded or shaped articles as described herein. Methods for molding the polyester composition into molded or shaped articles include any known methods in the art. Examples of molded or shaped articles of the present disclosure include, but are not limited to, thermoformed or thermoformable articles, injection molded articles, extrusion molded articles, injection blow molded articles, injection stretch blow molded articles, and extrusion blow molded articles. Methods for making molded articles include, but are not limited to, thermoforming, injection molding, extrusion, injection blow molding, injection stretch blow molding, and extrusion blow molding. The methods of the present disclosure may include any thermoforming method known in the art. The methods of the present disclosure may include any blow molding method known in the art, including, but not limited to, extrusion blow molding, extrusion stretch blow molding, injection blow molding, and injection stretch blow molding.

[0186] The present disclosure includes any injection blow molding manufacturing method known in the art. Although not limited thereto, a typical description of the injection blow molding (IBM) manufacturing method includes: 1) melting a composition in a reciprocating screw extruder; 2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; 3) moving the preform into a blow mold having a desired finished shape surrounding the preform and closing the blow mold surrounding the preform; 4) blowing air into the preform to stretch and expand the preform to fill the mold; 5) cooling the molded product; 6) ejecting the product from the mold.

[0187] The present disclosure includes any injection stretch blow molding manufacturing method known in the art. Although not limited thereto, a typical description of the injection stretch blow molding (ISBM) manufacturing method includes: 1) melting a composition in a reciprocating screw extruder; 2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; 3) moving the preform into a blow mold having a desired finished shape surrounding the preform and closing the blow mold surrounding the preform; 4) stretching the preform using an internal stretch rod and blowing air into the preform to stretch and expand the preform to fill the mold; 5) cooling the molded product; 6) ejecting the product from the mold.

[0188] The present disclosure includes any extrusion blow molding manufacturing method known in the art. Although not limited thereto, a typical description of an extrusion blow molding manufacturing method includes: 1) melting a composition in an extruder; 2) extruding the molten composition through a die to form a tube (i.e., a parison) of molten polymer; 3) clamping a mold having a desired finished shape around the parison; 4) blowing air into the parison to stretch and expand the extrudate to fill the mold; 5) cooling the molded article; 6) ejecting the article from the mold; and 7) removing excess plastic (commonly referred to as flash) from the article.

[0189] The following examples further illustrate how the polyesters of the present disclosure may be made and evaluated, and are intended to be illustrative only and not intended to limit the scope thereof. Unless otherwise indicated, parts are parts by weight, temperatures are in °C (degrees Celsius) or are at room temperature, and pressures are at or near atmospheric pressure.

[0190] The present disclosure includes and explicitly contemplates and discloses any and all combinations of the embodiments, features, characteristics, parameters and / or ranges mentioned herein. That is, the subject matter of the present disclosure can be defined by any combination of the embodiments, features, characteristics, parameters and / or ranges mentioned herein.

[0191] Any process / method, apparatus, compound, composition, embodiment or component of the present disclosure may be modified by the transitional words "comprising," "consisting essentially of," or "consisting of," or variations thereof.

[0192] As used herein, the indefinite articles "a" and "an" refer to one or more than one, unless the context clearly indicates otherwise. Similarly, nouns in the singular include their plural forms and vice versa, unless the context clearly indicates otherwise.

[0193] Although attempts have been made to be precise, the numerical values ​​and ranges described herein should be considered approximate unless the context otherwise indicates. These values ​​and ranges may deviate from their specified numbers depending on the desired properties that the present disclosure seeks to obtain and the variations caused by the standard deviations present in the measurement techniques. In addition, the ranges described herein are intended and explicitly contemplated to include all subranges and numerical values ​​within the specified ranges. For example, the range 50 to 100 is intended to include all numerical values ​​within the range, including subranges such as 60 to 90, 70 to 80, etc.

[0194] Any two numerical values ​​of the same property or parameter reported in the examples may define a range. These numerical values ​​may be rounded to the nearest thousandth, hundredth, tenth, integer, ten, hundredth or thousand to define a range.

[0195] The contents of all documents cited herein, including patents and non-patent documents, are hereby incorporated by reference in their entirety. If any incorporated subject matter conflicts with any disclosure herein, the disclosure herein shall take precedence over the incorporated content.

[0196] The present disclosure may be further illustrated by the following examples, but it should be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the present disclosure. Example

[0197] The oligomers used in these examples were prepared in a batch pilot plant and used as received. The composition evaluated was a copolyester of terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol, diethylene glycol, and neopentyl glycol. The concentrations of the diols were: 13 mol % NPG, 3 mol % 1,4-cyclohexanedimethanol, 5 mol % diethylene glycol, and the remaining 79 mol % was ethylene glycol. The oligomers were prepared at a total glycol / terephthalic acid molar ratio of 1.55 based on the weight of the total glycol loaded.

[0198] Each polyester sample was prepared by placing sufficient oligomer to make 100 grams of polyester in a 500 ml single neck round bottom flask. The target levels of titanium and antimony catalysts were added to the flask as an ethylene glycol solution along with the desired level of phosphorus. A stainless steel stirring unit consisting of a ¼” diameter shaft attached to a single 2.5” diameter stirring blade was inserted into the flask, and the flask was then fitted with a glass polymer head. A polymer head consisting of a standard tapered 24 / 40 male connector was connected to the reaction flask; a side arm was positioned approximately 45° to the flask neck to allow for the removal of volatile materials, and a section of glass tubing extended over the flask neck through which the stirring shaft passed. The section of tubing through which the stirring shaft passed was equipped with a Teflon bushing and a rubber hose to provide a vacuum tight seal around the stirring shaft. The shaft was rotated by a 1 / 8 horsepower electric motor connected via a flexible “universal” joint. The side arm was connected to a vacuum system consisting of a dry ice cooled condenser and a vacuum pump. The pressure in the reaction flask was controlled by introducing nitrogen into the vacuum stream. A molten metal bath was used to heat the reaction flask. All reaction parameters were monitored and controlled using a distributed data acquisition and control system.

[0199] Table 1 shows the reaction sequence used in all cases to prepare the polyester samples included in this evaluation.

[0200] Table 1

[0201] Reaction stage number Phase duration (minutes) Temperature(℃) Pressure (mm Hg) Stirring speed (RPM axis) 1 0.1 265 730 0 2 10 265 730 125 3 5 265 130 150 4 40 265 130 150 5 8 280 4 125 6 40 280 4 125 7 5 280, 290 or 300 1 75 8 53 280, 290 or 300 1 75 9 2 290 730 0

[0202] After synthesis, each polymer was removed from the blades of the stirring shaft and ground in a hammer mill to a particle size small enough to pass through a screen with 6 mm holes. All tests were carried out on the particles without further processing.

[0203] Table 2 below contains several examples of the disclosed catalyst system at various temperatures as well as eight control compositions prepared with pure titanium catalyst systems.

[0204] Table 2

[0205] Final reaction temperature (℃) IV L* a* b* Ti (ppm) P (ppm) Sb (ppm) P:Ti molar ratio The average value of 8 control samples 280 0.703 77.18 -0.23 20.07 25 23 0 1.35 Sample 1 280 0.709 77.2 -0.5 17.15 15 17 117 1.6 Sample 2 280 0.711 76.22 -0.55 15.78 10 15 123 2.2 Sample 3 280 0.65 78.41 -0.24 12.11 5 5 119 1.5 Sample 4 290 0.845 68.5 -0.56 15.94 10 9 127 1.4 Sample 5 290 0.757 68.62 -0.29 14.21 5 4 127 1.2 Sample 6 300 0.745 75.89 -1.14 11.07 13 48 110 5.8

[0206] The data in Table 2 show that the control pure titanium catalyst system (25 ppm Ti; 25 ppm P) has an average b* of about 20 at standard polymerization temperature (280°C). However, the b* data show improvement in all catalyst systems using Ti (5-15 ppm) and P (5-50 ppm) along with Sb (110-125 ppm). These results show that the polymers of the present invention have a lower b* or yellowness than the control resin made with titanium alone. At the standard polymerization temperature of 280°C, the inherent viscosity is comparable but the b* shows improvement and is below or less than 20. At higher temperatures (290°C and 300°C), both IV and b* show improvement, with higher inherent viscosities and b* still below or less than 20.

[0207] The inherent viscosity of the polyesters is measured herein at a concentration of 0.5 g / dL in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25°C and is reported in dL / g.

[0208] Copolyester resin samples were made using the procedure described herein. In all cases, the resin samples were dried prior to extrusion.

[0209] Laboratory film samples were made by extruding the resin samples into 10 mil (250 micron) films using a 2.5" Davis and Standard single screw extruder. These 10 mil films were cut and stretched on a Bruckner Karo 4 tenter frame at a temperature lower than the glass transition temperature (T g ) at a temperature of 5-15°C higher to a draw ratio of approximately 5:1 and a final thickness of 50 microns.

[0210] Tenter film samples were prepared by extruding and stretching resin samples on a commercial tenter (located at Marshall and Williams, a division of Parkinson Technologies) using a 3-layer ABC die extruded film with the B layer extruded from a 2.5-inch single screw extruder and the A and C layers extruded from separate 1.25-inch single screw satellite extruders. The film was cast at a thickness of approximately 10 mils (250 microns) and then stretched to a thickness of 50 microns at a 5:1 draw ratio. Typically, the cast thickness was 250 microns and the final film thickness was 50 microns. The line speed was 45 fpm.

[0211] The diol content of the extruded film compositions was determined by NMR. All NMR spectra were recorded on a JEOL Eclipse Plus 600 MHz NMR spectrometer using chloroform-trifluoroacetic acid (70-30 vol / vol) for the polymers, with deuterated chloroform added for locking. The acid component of the polymer blends used in the examples herein was 100 mol % terephthalic acid. The total mole percent of the diol component was equal to 100 mol % and the total mole percent of the acid component was equal to 100 mol %.

[0212] The inherent viscosity of the polyesters is measured herein at a concentration of 0.5 g / dL in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25°C and is reported in dL / g.

[0213] Shrinkage is measured here by placing a 50mm x 50mm square film sample in water at 5 degree increments between 65°C and 95°C (inclusive). The film is immersed in water for 10 seconds without restraining the shrinkage in any direction, and the shrinkage (or growth) of the film sample is measured. The % shrinkage is calculated by the following equation:

[0214] %Shrinkage rate = [(50mm-length after shrinkage) / 50mm]x100%.

[0215] Shrinkage is measured in the direction perpendicular to the main shrinkage direction (machine direction, MD) and also in the main shrinkage direction (transverse direction, TD).

[0216] For the examples herein, shrinkage force was measured in MPa using a LabThink FST-02 Thermal Shrinkage Tester at the same temperature used to stretch the film.

[0217] For the examples herein, tensile film properties were measured using ASTM method D882. The toughness of the films was evaluated using multiple film stretching speeds (300 mm / min and 500 mm / min).

[0218] The glass transition temperature and strain-induced crystalline melting point (T and T, respectively) of the polyesters were determined using a TA DSC 2920 from Thermal Analyst Instrument at a scanning rate of 20 °C / min. g and T m ). Tm was measured during the first heating of the stretched sample and T was measured during the second heating step. g Additionally, samples can be crystallized in a forced air oven at 165°C for 30 minutes and then analyzed by DSC. For all samples, there is generally no crystalline melting point during the second heating of the DSC scan at a heating rate of 20°C / min.

[0219] The compatibility of materials in recycling processes has been specified in the procedures published by the Association for Plastic Recyclers (APR). In the case of PETG resin, the agglomeration of PET is the main problem that has been solved by the present invention. A laboratory process was developed to simulate this industry standard. The parameters of the laboratory agglomeration test are as follows:

[0220] 582 g of PET bottle flakes were combined with 18 g of shrink flaked film in its shrunk state (3% film to PET bottle flakes) (the film was previously shrunk by soaking in water at 85°C for 10 seconds)

[0221] • Place the PET bottle flakes + film in an aluminum pan to a depth of 1.5 inches.

[0222] • Place the tray with the bottle pieces in a forced air oven at 208°C for 1.5 hours.

[0223] • The flakes were then carefully poured through a 0.5" sieve and the amount of flakes retained in the pan or that failed to pass through the sieve was weighed and the degree of caking (%) was calculated as a percentage of the starting weight.

[0224] The Association for Plastic Recyclers (APR) has established a test for measuring whether a material is compatible with existing recycling processes (Critical Guidance Protocol for Clear PET Articles with Labels and Closures PET-CG-02, revised or created on April 11, 2019). This method is based on a method for measuring PET flake clumping (PET Flake Clumping Evaluation; PET-S-08; revised on November 16, 2018). The details of this test are as follows:

[0225] • Grind labels (minimum 3% by weight, pre-shrunk at 85°C for 10 seconds) and bottles to ¼" to ½" chip size to produce labeled bottle flakes.

[0226] • Blend the labeled flakes with the unlabeled control flakes at a ratio of 50:50.

[0227] The sample was then elutriated with a setting that allowed a maximum of 1.2% PET to be labeled.

[0228] The pieces were washed with 0.3% Triton X-100 and 1.0% caustic soda at 88°C for 15 minutes.

[0229] • The flakes are then washed with water after all floating material has been removed and then strained to remove excess water.

[0230] Elute the flakes as before.

[0231] • Place 2 pounds of washed bottle flakes (with labels) in a Teflon-lined baking pan for each washed sample and add bottle flakes to a layer thickness of 1.5 inches.

[0232] Place the tray containing the bottle pieces in a circulating oven at 208°C for 1-1 / 2 hours.

[0233] The flakes are cooled and then passed through a screen with 0.0625 inch openings. As the material passes through the screen, there should not be any material that clumps and becomes too large to pass through the screen.

[0234] • This test is followed by extrusion / granulation and molding steps to ensure the quality of the flakes.

[0235] Modulated Differential Scanning Calorimetry (MDSC) is a technique that measures the difference in heat flow between a sample and an inert reference over time and temperature. Again, the same heat flux cell design as used in conventional DSC is used. However, in MDSC, different heating profiles (temperature regimes) are applied to the sample and reference. Specifically, a sinusoidal modulation (oscillation) is superimposed on the conventional linear heating or cooling ramp to produce a profile in which the average sample temperature varies continuously, but not linearly, over time. The net effect of applying this more complex heating profile to the sample is the same as running two experiments simultaneously on the material - one at a conventional linear (average) heating rate and one at a sinusoidal (instantaneous) heating rate. The actual rates of the two simultaneous experiments depend on three operator-selectable variables:

[0236] • Underlying heating rate (3°C / min)

[0237] • Modulation period (60 seconds)

[0238] • Modulated temperature amplitude (±1°C).

[0239] Glass transition temperature and melting peak area are analyzed using reversing heat flow. Heat of fusion (Hf) on heating is measured as the integrated reversing heat flow signal. Heat of crystallization (Hc) on heating is obtained by integrating the total heat flow signal. Relative crystallinity (C) of the sample is measured by subtracting heat of fusion (Hf) from heat of crystallization (Hc) on heating.

[0240] Examples 1-4

[0241] Copolyester resins with different diol compositions were made and converted into shrinkable films using a laboratory film process, and the corresponding shrinkable film properties were measured. The film samples were also tested for agglomeration with PET bottle flakes using a laboratory agglomeration test. The key performance attributes are shown below. Films made with Resin Examples 1 and 2 caused less than 1% agglomeration of PET bottle flakes. Films made with Resin Samples 1, 3, and 4 had excellent shrinkable film properties. Only the film made with Resin Example 1 had excellent shrinkable film properties and less than 1% agglomeration.

[0242] Table 3: Examples 1-4

[0243] Example 1 Example 2 Example 3 Example 4 PTA content (mol%) 100 100 100 100 EG content (mol%) 80 93.5 71 64 CHDM (mol%) 3 3.5 0 23 DEG content (mol%) 5 2 2 12 NPG content (mol%) 11 0 27 0 Total amorphous monomer content 19 5.5 29 35 Film thickness (micrometer) 50 50 50 50 Ultimate shrinkage (at 95°C) 73 24 79 80 MD shrinkage @ 70℃ (%) 6 1 -1 -3 Contraction force (MPa) 10 7.1 11 8.5 <![CDATA[T g (℃)]]> 74 78 77 69 Strain induced crystallization melting point (℃) 203 241 167 161 Elongation at break (%, at 300mm / min) 562 517 383 459 Elongation at break (%, at 500mm / min) 567 579 437 35 PET agglomeration (%) 0.8 0 10 25

[0244] Examples 5-7: Resin Examples 5-7 were made and converted into shrinkable films on a commercial tenter frame and tested for compatibility with PET recycling using the APR test procedure.

[0245] Table 4: Examples 5-7

[0246] Example 5 Example 6 Example 7 PTA content (mol%) 100 100 100 EG content (mol%) 80 79 76 CHDM (mol%) 3 3 17 DEG content (mol%) 5 5 6 NPG content (mol%) 11 13 0 Total amorphous monomer content 19 21 23 Film thickness (micrometer) 50 50 50 Ultimate shrinkage (at 95°C) 73 70 63 MD shrinkage @ 70℃ (%) 6 4 2 Contraction force (MPa) 10 10 8 <![CDATA[T g (℃)]]> 74 74 74 Strain induced crystallization melting point (℃) 203 196 194 Elongation at break (%, at 300mm / min) 562 470 451 Elongation at break (%, at 500mm / min) 567 429 580 PET agglomeration (%) 0.8 2.2 1.3% Heat of fusion (Hf, cal / g) 10.1 8.8 8.0 Heat of crystallization (Hc, cal / g) 0.4 0.4 0.3 Relative crystallinity (Hf-Hc, cal / g) 9.7 8.4 7.7

[0247] Examples 8-11: Resins based on Examples 8 to 11 were converted into shrinkable film samples and tested for shrinkable film properties and blocking with PET bottle flakes using a laboratory blocking test.

[0248] Table 5: Examples 8-11

[0249] Example 8 Example 9 Example 10 Embodiment 11 PTA content (mol%) 100 100 100 100 EG content (mol%) 80 79 79 88 CHDM (mol%) 5 15 0 5 DEG content (mol%) 5 5 5 7 NPG content (mol%) 10 0 16 0 Total amorphous monomer content 20 20 21 12 Film thickness (micrometer) 50 50 50 50 Ultimate shrinkage (at 95°C) 59 57 65 36 MD shrinkage @ 70℃ (%) 2 2 1 4 Contraction force (MPa) 9 9 9 6 <![CDATA[T g (℃)]]> 75 76 74 74 Strain induced crystallization melting point (℃) 200 201 196 227 Elongation at break (%, at 300mm / min) 588 643 552 566 Elongation at break (%, at 500mm / min) 675 636 493 598 PET agglomeration (%) 0.5 0.7 3.8 0.5 Heat of fusion (Hf, cal / g) 8.2 10 9.5 13.9 Heat of crystallization (Hc, cal / g) 0.3 0.2 0.4 0.5 Relative crystallinity (Hf-Hc, cal / g) 7.8 9.9 9.2 13.4

[0250] Examples 12-16: Multilayer films were made using a commercial tenter frame process and tested for blocking with PET bottle flakes using a laboratory blocking test. These films were made using Example 4 as the core layer and Example 1 as the cover layer.

[0251] Table 6: Multilayer Films, Examples 12-16

[0252] Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Example 16 PTA content (mol%) 100 100 100 100 100 EG content (mol%) 64 67 67 68 69 CHDM (mol%) 23 20 18 17 15 DEG content (mol%) 12 11 10 9 9 NPG content (mol%) 0 3 4 5 7 Total amorphous monomer content 35 31 28 31 31 Covering layer(%) 0 9 13 16 20 Core layer(%) 100 91 87 84 80 Film thickness (micrometer) 50 50 50 50 50 Ultimate shrinkage (at 95°C) 80 77 77 77 77 MD shrinkage @ 70℃ (%) -4 -3 -3 -4 -4 Contraction force (MPa) 6.0 7.7 7.0 7.8 7.2 <![CDATA[T g (℃)]]> 68 70 69 70 70 Strain-induced crystallization melting point (℃) #1 159 167 157 158 158 Strain induced crystallization melting point (℃) #2 N / A 217 217 217 217 Elongation at break (%, at 300mm / min) 503 436 440 438 417 Elongation at break (%, at 500mm / min) 129 359 374 454 448 PET agglomeration (%) 25 18 19 31 26

[0253] Thermoformed sheet embodiment:

[0254] Examples A, B, and C were extruded into sheets having a thickness of 30 mils (750 microns) using a 2.5" Davis and Standard extruder. The sheet samples were then thermoformed into a basic tray design (dimensions 169 mm x 136 mm x 44 mm) using an aluminum female die designed to allow vacuum assist through the form. The form was mounted on a Hydrotrim laboratory thermoformer. The oven temperature and die temperature were held constant at 260°C and 42°C, respectively. The sheet samples were placed in the oven for various residence times, removed from the oven, immediately formed into trays, and allowed to cool before being removed from the die. The sheet temperature was measured using an infrared temperature sensor that is part of the thermoformer and confirmed with a handheld infrared thermometer.

[0255] The dwell time was varied to establish a thermoforming window within which high quality parts could be made, starting at 15 seconds and increasing by 2 seconds each time. The dwell time was varied to allow the samples to be heated to different temperatures prior to forming. Testing was stopped after the dwell time reached 29 seconds because Example C was very hazy and was not considered a viable tray. The haze of each sample was measured as an indication of part quality and crystallinity.

[0256] The tray made from Example C began to show slight haze at 23 seconds residence time. This indicates that Example C has a smaller thermoforming window compared to Examples A and B, as Examples A and B did not show an increase in haze over this residence time range. The quality of the thermoformed parts is marked with a "+" to indicate acceptable quality or a "-" to indicate poor quality. These quality grades are based on a combination of haze and part definition after thermoforming.

[0257] Samples of extruded sheets and thermoformed parts were evaluated for compatibility with PET recycling using a laboratory agglomeration procedure. In addition, a pre-crystallization step was used as described in the APR screening test for PET agglomeration. Results from this agglomeration test are shown.

[0258] Example B exhibits desirable and distinguishing characteristics: a wider thermoforming window, making it easier to process; and the ability to crystallize during recycling, making it compatible with PET recycling processes.

[0259] Table 7: Thermoformable sheet composition

[0260] Example# A B C PTA content (mol%) 100 100 100 EG content (mol%) 69 79 93 NPG (mol%) 0 13 0 CHDM (mol%) 30 3 4 DEG content (mol%) 1 5 3 Total amorphous monomer content (mol%) 31 21 7

[0261] Table 8: Thermoformed sheet quality

[0262] sample Soaking time, s Sheet temperature, °C Component quality %Haze Example A 15 114 - 0.7 Example A 17 123 - 0.64 Example A 19 129 + 0.68 Example A 21 138 + 0.67 Example A 23 145 + 0.62 Example A 25 152 + 0.72 Example A 27 156 + 0.77 Example A 29 162 + 0.51 Example B 15 114 - 0.54 Example B 17 123 - 0.69 Example B 19 129 + 0.59 Example B 21 138 + 0.64 Example B 23 143 + 0.57 Example B 25 148 + 0.56 Example B 27 156 + 0.52 Example B 29 162 + 0.75 Example C 15 114 - 1.19 Example C 17 124 - 1.38 Example C 19 131 + 1.43 Example C 21 138 + 1.52 Example C 23 143 - 2.18 Example C 25 153 - 4.17 Example C 27 157 - 12.07 Example C 29 163 - 30.07

[0263] Table 9: Laboratory PET agglomeration of thermoformed sheets (%)

[0264] Extruded sheet Thermoformed parts Pre-crystallization Example A 8.8% 11.0% N / A Example B 4.2% 6.7% 0.1% Example C 0.6% 0.5% 0.2%

[0265] Injection molding samples:

[0266] Samples A, B, C and Examples 1 and 3 were injection molded and tested for mechanical properties using normal injection molding procedures known to those skilled in the art. The test parts were tested according to the following test methods: ASTM D638, ASTM D3763, ASTM D256, ASTM D4812, and ASTM D64. The mechanical properties of the injection molded parts made with these reactor grade resins are shown in Table 10.

[0267] Table 10: Mechanical properties of injection molded parts

[0268] Sample A Sample B Sample C Example 1 Example 3 <![CDATA[T g (℃)]]> 73 75 79 76 68 Yield strength, MPa 50 57 57 57 54 Yield strain, % 4 4 4 4 4 Breaking strength, Mpa 24 21 23 20 16 Fracture strain, % 100 84 90 51 18 Modulus, MPa 2061 2377 2364 2397 2202 Notch 23℃ 73 31 46 30 50 Gap -40℃ 37 32 31 31 35 No gap 23℃ 2514 2760 2656 2707 2572 No gap -40℃ 2933 1374 1953 925 2423 Instrumented shock 23°C, energy @ maximum load 37 32 34 32 32 Instrumented shock -40°C, energy @ maximum load 48 2 3 2 43 HDT @ 1.82 MPa 61 58 30 60 55 HDT @ 0.455 MPa 68 63 66 65 58

[0269] The invention has been described in detail with particular reference to preferred embodiments thereof, but it will be understood that variations and modifications can be effected within the spirit and scope of the disclosure.

Claims

1. A reactor-grade polyester composition comprising at least one polyester, wherein the at least one polyester comprises: (a) a dicarboxylic acid component comprising: (i) 70 to 100 mole percent of terephthalic acid residues; (ii) 0 to 30 mol % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: 80 mol% or more of ethylene glycol residues and 20 mol% or less of other diols, the other diols comprising: (i) 5 to less than 17 mole % neopentyl glycol residues; (ii) 2 to less than 10 mole % 1,4-cyclohexanedimethanol residues; (iii) 1 to less than 5 mole % of diethylene glycol residues; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system comprising 2 to 15 ppm titanium, 50 to 150 ppm antimony, and 0 to 90 ppm phosphorus, wherein the concentration of the residue of the catalyst system is based on the weight of the polyester.

2. The reactor-grade polyester composition of claim 1, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system comprising 3 to 10 ppm titanium, 50 to 125 ppm antimony, and 0 to 60 ppm phosphorus, wherein the concentration of the residue of the catalyst system is based on the weight of the polyester.

3. The reactor-grade polyester composition of claim 1, wherein the reactor-grade polyester composition further comprises a residue of a catalyst system comprising 4 to 12 ppm titanium, 100 to 120 ppm antimony, and 2 to 50 ppm phosphorus, wherein the amount of the residue of the catalyst system is based on the weight of the polyester.

4. The reactor-grade polyester composition of claim 1, wherein the reactor-grade polyester composition has a strain-induced crystallization melting point of 190°C or higher.

5. The reactor-grade polyester composition of claim 1, wherein the reactor-grade polyester composition has a strain-induced crystallization melting point of 200°C or higher.

6. A method for preparing the reactor-grade polyester composition of claim 1, comprising: (a) reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues and ethylene glycol residues in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound to produce an esterified product; wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; (b) prepolymerizing the esterification product in the presence of 0 to 90 ppm of a phosphorus stabilizer to prepare a polycondensation product, wherein the prepolymerization temperature is 255 to 275° C. and the pressure is 200-500 mmHg; (c) post-treating the polycondensation product to produce a polyester, wherein the polyester has an inherent viscosity of at least 0.50 dL / g, and wherein the post-treatment polymerization temperature is elevated at 280-320° C. and the pressure is 0.3 to 7 mmHg.

7. A method for preparing the reactor-grade polyester composition of claim 1, comprising: (a) reacting a diacid component comprising terephthalic acid residues with a diol component comprising neopentyl glycol residues, 1,4-cyclohexanedimethanol residues, diethylene glycol residues, and ethylene glycol residues to produce an esterified product, wherein the esterification reaction temperature is 240 to 270° C. and the pressure is 5 to 50 psi; (b) prepolymerizing the esterified product in the presence of 2 to 15 ppm of a titanium compound, 50 to 150 ppm of an antimony compound, and 0 to 90 ppm of a phosphorus stabilizer to prepare a prepolymerized polycondensation product, wherein the polycondensation temperature is 255 to 275° C.; and (c) post-treating the polycondensation product to produce a polyester, wherein the polyester has an inherent viscosity of at least 0.50 dL / g, and wherein the post-treatment polymerization temperature is elevated from 280 to 320° C. and the pressure is from 0.3 to 7 mmHg.

8. The method according to claim 6 or 7, wherein the titanium compound is selected from titanium tetraalkoxide, tetraalkyl titanate and mixtures thereof, or wherein the antimony compound is one or more of antimony trioxide, antimony acetate or antimony oxalate; or The phosphorus stabilizer is phosphoric acid, phosphorous acid, phosphonic acid, phosphinic acid, phosphous acid or esters or salts thereof.

9. The method according to claim 6 or 7, wherein the titanium compound is selected from titanium tetraisopropoxide, titanium tetraethoxide, titanium tetrabutoxide, tetraisopropyl titanate and mixtures thereof, or The phosphorus stabilizer is a phosphate ester.

10. The method according to claim 9, wherein the phosphorus stabilizer is trialkyl phosphate, triphenyl phosphate or tris(nonylphenyl) phosphite.

11. The method of claim 6, wherein the method further comprises dissolving an antimony compound in one of the diols.

12. The method according to claim 6 or 7, wherein the post-treatment polymerization temperature is 290°C or 300°C.

13. The process of claim 6, wherein the titanium compound and the antimony compound are added together and the phosphorus stabilizer is added as a separate feed.

14. The method according to claim 7, wherein the titanium compound, the antimony compound and the phosphorus stabilizer are added after the esterification of terephthalic acid.

15. The method of claim 6, wherein the antimony compound is dissolved in one of the diols; or wherein the titanium compound is dissolved in one of the diols or in butanol.

Citation Information

Patent Citations

  • Microporous polymeric films and process for their manufacture

    EP0214859A2

  • Biaxially oriented, laminated polyester film

    EP0581970B1

  • Synthetic resin film for printing

    JP1986037827A

  • Shrinkable film

    JP1988193822A

  • Heat shrinkable polyester type film roll and its manufacturing process

    JP2004181863A